Temperature-fluctuation effects on shrimp protein quality assessed via a multi-stage temperature-fluctuation protein convolutional neural network - Zhexun Yang; Yiling Zhang; Sili Xiao; Weiteng Weng; Ziqi Xie; Jiayi Li; Wen Jie Li; Ying Deng; Yutao Wei; Yudan Li; Shuangyin Liu; Xuekai Gao; et al. (Journal of Food Engineering, 2027)

Secondary metabolites from the heartwood of Toxicodendron vernicifluum (Stokes) F. A. Barkley (Anacardiaceae) and their chemotaxonomic significance - Cai-Wen Meng; Chun-Zhi Zhao; Jie Liu; Wen-Jing Zu; Hong-Yun Bai; Jian-Yu Liu; Yong-Nan Xu; Mei-Chen Li (Biochemical Systematics and Ecology, 2026)

Mechanistic insights into metallic iron-induced changes in viscosity, structure, and iron agglomeration of fixed-bed gasifier slag - Chuang Wu; Ji Wang; Jin Bai; Lingxue Kong; Zhenxing Guo; Huaizhu Li; Zongqing Bai; Wen Li (Fuel, 2026)

A TMAI5 polyhalide as a multifunctional cathode enabling three-electron transfer with synergistic I/Cl interaction for aqueous dual-ion batteries - Weiye Bai; Zhiyu Wen; Mingqiang Li; Mingyang Cao; Jiawei Li (Chemical Engineering Journal, 2026)

Formation of post-traumatic and non-traumatic knee joint contracture: Role of macrophage polarization in joint capsule and skeletal muscle - Feng Wang; Fan Bai; Ting Zhou; He Liu; Ding-Jiang Wu; Yun Zhou; Wen Li (Tissue and Cell, 2026)

Bottom-up construction of betaine-grafted iCOF: Selective adsorption of Cr(VI) via precise host-guest interaction - Zhihui Wen; Erli Ding; Yongjie Bai; Xiaochan Liu; Yourong Wei; Ge Li; Benhua Xu; Bingxin Liu (Chemical Engineering Journal, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Village-level multi-objective optimization of wheat and maize area constraints: Balancing irrigation water use, carbon intensity, and farm income - Jianhu Lei; Dan Bai; Zhangning Xu; Li Li; Xueli Bai; Wen Zhou (Agricultural Systems, 2026)

First report of mass mortality in post-metamorphosis Magallana gigas associated with OsHV-1 in China: epidemiological and genomic characterization - Bo-Wen Huang; Xiang Zhang; Tao Xu; Yi-Tao Zhang; Xiao-Ai Li; Lei Gao; Ning Kong; Ming-Kun Liu; Tao Yu; Hui-Gang Kang; Chong-Ming Wang; Chang-Ming Bai (Journal of Invertebrate Pathology, 2026)

Solvent-toughened ultra-stretchable poly(ionic liquid) gels for multifunctional wearable bioelectronics - Yongkang Bai; Xiaoli Liang; Didi Wen; Zhoujing Chen; Chi Zhang; Zhun Hu; Wei Fan; Yuqi Li (Chemical Engineering Journal, 2026)

Redox-sensitive genetic circuits enhance microbial stress tolerance to complex inhibitors in lignocellulose biorefinery - Wen-Tao Wang; Qi Feng; Ting-Ting Li; Muhammad Aamer Mehmood; Hui Zhu; Ning Wang; Yi Ma; Chen-Guang Liu; Feng-Wu Bai (Chemical Engineering Journal, 2026)

Evolution and formation pathways of volatiles during co-pyrolysis process of coal and various polymers based on ReaxFF MD simulation and in-situ Py-TOF-MS - Wei Feng; Xiaodong Chen; Jin Bai; Mo Zheng; Jinjun Guo; Congbin Jiang; Xianxian Zhang; Zongqing Bai; Wen Li (Chemical Engineering Journal, 2026)

CaHAT5, an HD-ZIP transcription factor, positively regulates capsaicinoid biosynthesis during pepper fruit development - Miao Li; Jiaqin Li; Yongqing Bai; Qing Wen; Shiyu Tian; Muhammad Safiullah Virk; Yinghui Hou; Xinzhuan Yao; Yumei He; Litang Lu (Plant Science, 2026)

Catalytic upgrading of Hami coal pyrolysis volatiles over NiO-loaded calcined/acid/alkali-modified kaolin - Yujie Hou; Zongqing Bai; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Fuel, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

The maternal gut microbiota influences myocardial maturation and diastolic function of offspring in mice - Shanshan Li; Yiqiong Zhang; Yang Li; Yuyang Lei; Hao Wu; Peining Liu; Wen Xi; Xiaozhen Zhuo; Pu Huang; Ting Yang; Ting Bai; Juanli Li; et al. (Science China Life Sciences, 2026)

Intelligent optimization of soil conditioning schemes based on earth pressure balance shield tunnelling data - Xin Wang; Wen Zhao; Jialong Li; Jianyong Han; Cheng Cheng; Qian Bai; Dazeng Sun (Tunnelling and Underground Space Technology, 2026)

Effect of bentonite slurry on muck discharge performance of EPB shield screw conveyor - Xin Wang; Wen Zhao; Qian Bai; Dazeng Sun; Ying Wang; Jialong Li (Tunnelling and Underground Space Technology, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

An experimental and kinetic modeling study of the autoignition delay times of triethyl phosphite - Frederick Nii Ofei Bruce; Yuke Gao; Ruining He; Zhihan Zhu; Xin Wang; Yilin Zhao; Mengmeng Jia; Jiaxin Xie; Xin Bai; Yun Hin Taufiq-Yap; Chong-wen Zhou; Henry Curran; et al. (Fuel, 2026)

Effects of personality and body weight on foraging behavior and vigilance: a case study in a small rodent - Yu-Chuang Hui; Shu-Jing Gao; Xuan-Wen Li; Wei-Qi Chen; Yue-Yue Yang; Xue-Dong Bai; Qin Su; Fu-Shun Zhang; Li-Qing Wang; Ling-Ying Shuai (Behavioral Ecology and Sociobiology, 2026)

CaCDF3 Positively Regulates Capsaicinoids Biosynthesis Under Drought Stress in Capsicum annuum - Jiaqin Li; Miao Li; Qing Wen; Yongqing Bai; Xinzhuan Yao; Muhammad Safiullah Virk; Shiyu Tian; Shilai Tian; Hufang Chen; Yumei He; Jianjian Wang; Litang Lu (Journal of Plant Growth Regulation, 2026)

Identification of Metabolism-Related Genes with Potential Diagnostic Value in Gestational Diabetes Mellitus - Yan Mo; Yan-Yuan Bai; Xiu-Fang Li; Hua Zhang; Juan Liang; Wen-Juan Zhang; Li Lu; Wan-tao Liang (Indian Journal of Clinical Biochemistry, 2026)

Rheological experiment and transport simulation of conditioned soil in EPB shield tunneling through fully weathered granite strata - Qian Bai; Jingmin Xu; Wen Zhao; Jialong Li; Qinghai Yang; Huan Liu (Tunnelling and Underground Space Technology, 2026)

Fairness-constrained influence maximisation via multi-objective optimisation - Ziying Zhao; Weihua Li; Jing Ma; Jianhua Jiang; Quan Bai; Wen Gu (Swarm and Evolutionary Computation, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

A hierarchical machine learning framework for reconstructing freezing-period pan evaporation across various climate zones of China - Wenhui Jiang; Bingxue Dong; Qingqing Sui; Zhenlin Lai; Lei Wen; Zhentao Bai; Zhijun Li; Junliang Fan (Journal of Hydrology, 2026)

Coaxial electrospun TiO2@CuO heterojunctions with interfacial charge rearrangement for photothermal oxidation of toluene - Weimin Huang; Ke-Xin Li; Shuzhuo Bai; Shanshan Chen; Fanbin Meng; Bing Qin; Yuning Yang; Zonghui Liu; Wen-Tao Zheng; Zhun Hu (Journal of Environmental Chemical Engineering, 2026)

An experimental study on the ignition and combustion characteristics of ultrafine boron particles - Ruining He; Xin Bai; Xuan Ren; Yilin Zhao; Xin Wang; Jinhu Liang; Fei Qin; Ce Sun; Taufiq Yap Yun Hin; Chong-Wen Zhou; Henry J Curran; Yang Li (Fuel, 2026)

The charge compensation effect of K+ to the tetrahedrally coordinated Al3+ in the slag determines the K release behavior in the condition of slag-tapping - Jing Guo; Chong He; Xiaoming Li; Mengran Yuan; Alexander Ilyushechkin; Yulong Zhang; Jin Bai; Wen Li (Fuel, 2026)

The study of viscosity behavior of anorthite-bearing slag under gasification conditions based on slag structure analysis - Hao Lu; Jin Bai; Wenju Shi; Jingpei Cao; Lingxue Kong; Huaizhu Li; Wen Li (Fuel, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

A mechanistic machine learning framework to decode reverse osmosis membrane retention mechanism for neutral low-molecular-weight organics - Han-Ying Cai; Yin-Hu Wu; Bai-Wen Ma; Hui Li; Pei-Hua Li; Qian-Yuan Wu; Wen-Long Wang; Zhuo Chen; Hong-Ying Hu (Journal of Cleaner Production, 2026)

Reuse of discharged silty clay from EPB shield tunnel construction as soil conditioning material - Wen Zhao; Xin Wang; Qian Bai; Dazeng Sun; Wenxin Cao; Jialong Li (Bulletin of Engineering Geology and the Environment, 2026)

Planar chiral [2.2]paracyclophane biarylphosphine (PCP-BPhos) libraries: rational design, catalytic synthesis, and applications - Mingjie Li; Jingyi Bai; Hong-Yu Qu; Wen-Hua Zheng; Minyan Wang; Zhuangzhi Shi (Science Bulletin, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Distribution pattern and development of typical antibiotic resistance genes in the continuous-flow aerobic granular sludge-membrane bioreactor system - Yongsheng Jiang; Yu Zeng; Lei Shang; Dehong Bai; Liying Bin; Weirui Chen; Xinyi Chen; Shanglong Wen; Shaosong Huang; Ping Li; Bing Tang (Journal of Environmental Chemical Engineering, 2026)

Carbon quantum dots-loaded potassium titanate nanotubes efficiently activate peracetic acid through radical and non-radical pathways for pefloxacin degradation - Ruopu Bai; Chaofan Song; Li Ma; Jie Zhao; Guangcan Zhu; Hongyang Wang; Weiliang Sun; Wen Liu (Journal of Environmental Chemical Engineering, 2026)

Waste agricultural mulch film-derived porous carbon-based catalysts for efficient industrial wastewater purification - Yimin Zhu; Xie Li; Tengfei Shao; Mingzhu Chen; Wen Wang; Zhaoxuan Feng; Shibing Bai; Weijun Zhen; Zhiqing Liu (Journal of Environmental Chemical Engineering, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Pyroptosis as a double-edged sword in colorectal cancer: Molecular mechanisms and therapeutic opportunities - Han-Xi Zhang; Wen-Jing Xu; Yi-Xin Jiang; Lu Li; Bai-Yu Chen; Meng-Yao Cheng; Meng-Yuan Hao; Hang-Shen Han; Hong-Jie Li; Yan-Ge Li; Dong-Dong Wu (Apoptosis, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Visco-elastic interface and dynamic response of a lined tunnel in anisotropic rock mass under unloading waves - Xue-Qian Fang; Zhao-Feng Zhong; Bai-Lin Li; Xin-Yu Liu; Ya-Wen Xiong (Soil Dynamics and Earthquake Engineering, 2026)

Emission reduction optimization of recycling pathways for retired photovoltaic modules in China: A coupled model of life cycle assessment and evolutionary game theory - Xu Zhu; Yichen Li; Yue Zhang; Yuanyuan Sun; Wen Xu; Lu Bai (Journal of Cleaner Production, 2026)

Pyrolysis behavior of solvent-extracted group components from coking coal: Insights into volatile release and source contributions to coke formation - Tingting Zhang; Xingjin Zhang; Haoyu Dou; Shujun Wang; Zongqing Bai; Jin Bai; Wen Li (Fuel, 2026)

Synergistic quorum quenching effect and mechanism of penicillin G acylase combined with chlorogenic acid against Hafnia alvei and their application in salmon fillets preservation - Xinran Lv; Hengli Xu; Yichang Sun; Xin Wen; Minghan Shan; Wenjin Yan; Qihan Bai; Sicheng Li; Siyan Du; Xuepeng Li; Jianrong Li; Hung-chuan Chiu (Food Bioscience, 2026)

Achievement of broadband microwave absorption and infrared stealth in PEEK composites with a low filling ratio via a hierarchical design - Yashu He; Fengyu Wen; Yageng Bai; Yifan Wang; Jierun Ma; Haoyuan Tan; Yuxuan Gu; Pengbo Lian; Lei Li; Hailiang Yang; Jianxin Mu (Chemical Engineering Journal, 2026)

Proanthocyanidin B2 regulates epidermal growth factor receptor (EGFR) and activates the PI3K/AKT pathway to promote the in vitro maturation of sheep oocytes - Yucheng Liu; Jingjing Wang; Zhenliang Zhang; Jiachen Bai; Houru Li; Zhanmin Lv; Lei Gao; Jianhong Ni; Shouliang Lu; Changbin Liu; Guiping Hai; Weijun Liu; et al. (Theriogenology, 2026)

Controllable synthesis of hierarchical pores of carboxyl-functionalized coconut shell activated carbon and its formaldehyde adsorption properties - Xiaoyu Wen; Mingshu Chi; Li Bai; Jiankai Liu; Bochong Sun (Journal of Environmental Chemical Engineering, 2026)

Unraveling the thermal decomposition kinetics of triethyl phosphite - Frederick Nii Ofei Bruce; Xin Wang; Xin Bai; Minjie Wen; Dongping Chen; Song Cheng; Henry Curran; Yang Li (Fuel, 2026)

Formation and characteristics of condensable particulate matter from combustion of Zhundong high-sodium coal - Chunhao Cai; Yujun Guo; Lingxue Kong; Lei Huang; Zhenxing Guo; Jin Bai; Wen Li (Fuel, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

A novel blended adsorbent granule of crown ether polymer mixed with Mn-based lithium-ion sieves for efficient lithium recycling from shale gas wastewater - Xifan Li; Xin Li; Mingmei Zheng; Jialin Shi; Lu Yang; Yushun Yang; Guijing Chen; Shengchi Bai; Xiao Lin; Wen Liu; Baicang Liu (Desalination, 2026)

Cadzow Filtering Method Based on Adaptive Singular Value Decomposition - Zhong-lin Cao; Dan Wang; Peng-yuan Sun; Le Li; Ding-yu Xiong; Wen Yang; Yin-yu Wen; Jing Bai (Applied Geophysics, 2026)

Attenuation and disturbances of surface and coal seam seismic waves caused by ground deep-hole blasting - Xianxi Bai; Anye Cao; Xueqi Zhang; Xufeng Qin; Yingshi Gu; Geng Li; Chengchun Xue; Yingyuan Wen (Soil Dynamics and Earthquake Engineering, 2026)

Structure–tuned, phosphorus–doped hierarchical porous biochar via green hydrothermal carbonization and activation for formaldehyde adsorption - Bochong Sun; Mingshu Chi; Li Bai; Jiankai Liu; Xiaoyu Wen (Fuel, 2026)

Effect of the briquetting process on the pyrolysis characteristics and product properties of the briquette prepared by municipal sludge and low-rank coal - Peilong Gao; Zongqing Bai; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Fuel, 2026)

Associations of PM2.5 carbonaceous and ionic constituents with fractional exhaled nitric oxide (FeNO): A panel study with 16 follow-up visits over 4 years - Nan Zhang; Yuqi Guo; Deyan Wu; Zinuo Li; Jialin Wang; Nan Zhang; Jia Xu; Xueli Yang; Qiang Zhang; Changping Li; Shi Zhao; Xumei Zhang; et al. (Environmental Research, 2026)

Chemical constituents from the fruits of Toxicodendron vernicifluum (Stokes) F. A. Barkley (Anacardiaceae) and their chemotaxonomic significance - Wenjing Zu; Lu Guan; Jie Liu; Cai-Wen Meng; Hongyun Bai; MeiChen Li; Jianyu Liu; Yongnan Xu (Biochemical Systematics and Ecology, 2026)

Low-dose lipopolysaccharide modulates the RNF4-induced SUMO-dependent degradation of Nrf2 to mitigate oxidative stress in spinal cord injury - Weibing Liu; Kun Huang; Yuncheng Bai; Yayu Zhao; Wen Lei; Hongran Ge; Weichao Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Occurrences and migration characteristics of photoinitiators in paper food packaging: Implication for human exposure - Chenge Qian; Lu Bai; Wen Wang; Yadan Luo; Juan Li; Yawei Wang (Journal of Environmental Sciences, 2025)

Sintering mechanism of the coal fly ash particle revealed from the compressive strength - Xiaoming Li; Yujun Guo; Shiyin Feng; Chong He; Huaizhu Li; Jin Bai; Wen Li (Fuel, 2025)

A review on migration behavior and safety regulation of inorganic nanoparticles in food packaging: Multi-scale mechanisms, risk assessment, and innovative strategies - Jingjing Wang; Xu Liang; Huanhuan Hou; Jing Deng; Qinlu Lin; Wen Li; Jie Bai (Food Control, 2025)

Cloud-based SHM of transmission tower via micro image strain sensing - Bo Lu; Bingchuan Bai; Pengfei Wu; Huan Li; Han Yuan; Zhichao Wen; Weijie Li; Xuefeng Zhao (Engineering Structures, 2025)

Fatigue-resistant, self-healing and antibacterial poly(ionic liquid) gel multichannel sensors for underwater early warning and deep learning-assisted infant monitoring - Xiaoli Liang; Longzhang Niu; Jinhan Song; Zhoujing Chen; Hongwang Qu; Didi Wen; Yuqi Li; Lina Niu; Yongkang Bai (Chemical Engineering Journal, 2025)

Phenolics from Toxicodendron vernicifluum (Stokes) F. A. Barkley (Anacardiaceae) and their chemotaxonomic significance - Cai-Wen Meng; Wen-Jing Zu; Jie Liu; Xue Qiu; Hong-Yun Bai; Jian-Yu Liu; Yong-Nan Xu; Mei-Chen Li (Biochemical Systematics and Ecology, 2025)

Commentary on “CircMAPK1 induces cell pyroptosis in sepsis-induced lung injury by mediating KDM2B mRNA decay to epigenetically regulate WNK1” - Wen-jing Bai; Chen-guang Li (Inflammation Research, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Innovative calibration transfer methods and comprehensive application strategies for multi-brand FT-MIRS instruments in milk component analysis - Yikai Fan; Zhuo Yang; Dongwei Wang; Peipei Wen; Chu Chu; Guochang Yang; Haitong Wang; Tingting Liu; Wenjuan Bai; Yao Liu; Jiawei Li; Shujun Zhang (Computers and Electronics in Agriculture, 2025)

Overlooked synergisms of flotation organic reagents and toxic metals in water: Formation of tridentate cadmium-xanthate complexes - Lei Xiang; Qian-Wen Wang; Wen-Jun Wu; Nian-Jue Zheng; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; Qing X. Li (Water Research, 2025)

Innovative application of SDCM-PHC integrated pile-column system in semi-cover excavation metro stations: Mechanical behavior and performance validation - Xiujie Tang; Wen Zhao; Jiaxiang Li; Lili Jiao; Changlong Guo; Qian Bai; Bo Lu (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Predictive biomarkers for valproic acid-induced hepatotoxicity in Chinese patients with epilepsy: the role of metabolites and genetic polymorphisms - Dingsheng Wen; Zhuojia Chen; Ziyi Chen; Xue Bai; Hongliang Li; Juan Chen; Qiling Dai; Guoping Zhong; Jiaming Qin; Guanzhong Ni; Min Huang; Liemin Zhou; et al. (Food and Chemical Toxicology, 2025)

Sustainable and selective capture of Ca2+/Mg2+ from seawater desalination brines via hierarchical chitosan-based biochar aerogel adsorption - Wenjie Wang; Xin Li; Jiawang Qin; Chunyan Yang; Quanxun Liang; Shun Tang; Zhaoying Li; Jiale Wang; Shengchi Bai; Xiaoqi Wang; Wen Wen; Baicang Liu (Desalination, 2025)

When AI meets AIE: Machine learning in design function-oriented AIEgens for antibacterial ability - Leina Dou; Penghui Zhou; Fei Qi; Qing Li; Yuchen Bai; Liang Luo; Kai Wen; Wenbo Yu; Xuezhi Yu; Jianzhong Shen; Zhanhui Wang (Chemical Engineering Journal, 2025)

Rapid increase in carbon sink from China’s urban forests - Weixiang Cai; Nianpeng He; Li Xu; Hongbo Guo; Zhenghu Zhou; Ding Wen; Xiaoyong Bai; Guirui Yu (Science Bulletin, 2025)

Oxidative pyrolysis of biomass waste: Efficient production of humic substances with enhanced agricultural potential and environmental benefits - Jian Li; Wen Fu; Xiaowei Bai; Ning Mao; Xiangrui Lin; Heping Yang; Mengfei Wang; Guangxuan Liu; Zhenghua Dai (Journal of Cleaner Production, 2025)

Effects of fertilization and different straw return methods on soil fertility and rice yield in double-season paddy fields - Nan Zhang; Jiong Wen; Lingyu Bai; Xiaxin Wei; Tao Li; Yuefeng Tang; Shiming Su; Zhi Peng; Xibai Zeng (Journal of Environmental Chemical Engineering, 2025)

In situ FeF3 coating on FeNCN to stabilize discharged products Fe0 for enhanced loading and high-rate Na storage performance - Jiayin Li; Wen Wen; Shuzhuo Bai; Jing Zhang; Chenyu Wu; Jintao Wu; QingQing Huang; Yalin Zhang; Chunyi Cai; Liyun Cao; Yijun Liu; Haibo Zhang; et al. (Chemical Engineering Journal, 2025)

Engineering in-plane defects in VS2-X for fast Na+ transport and highly active NaS reaction in thick electrodes - Liyun Cao; Chunyi Cai; Jianfeng Huang; Yiting Wang; Dewei Chu; Yijun Liu; Yong Zhao; Junle Dong; Qingqing Huang; Yalin Zhang; Shuzhuo Bai; Wen Wen; et al. (Chemical Engineering Journal, 2025)

Global burden and characterization of hypertriglyceridemia-induced acute pancreatitis: results from a systematic review and a multi-center cohort study - Zhengyang Fan; Yuelun Zhang; Jianing Li; Wenhua He; Xiaoyin Bai; Yanna Cai; Naishi Li; Feng Xie; Li Wen; Venkata Sandeep Akshintala; Yin Zhu; Dong Wu (Science China Life Sciences, 2025)
To compare and characterize hypertriglyceridemia-induced acute pancreatitis (HTG-AP) across the geographical regions, we conducted a systematic review and a multi-center cohort study. We conducted a systematic review and random effects meta-analysis of studies reporting HTG-AP. Also, we separately characterized HTG-AP in a multi-center retrospective cohort study involving eight centers in China. The key outcomes of interest included the pooled proportion of HTG-AP and its severity parameters after adjusting for the effect of confounding factors through logistic regression. Our systematic review identified 110 studies from 15 countries accounting for 3,057,428 participants (35% female, median age 50 years). The pooled proportion of HTG-AP was 11.6% globally while the Eastern and Western countries reported the proportions as 16.3% and 5.4%, respectively ( P <0.01). The pooled mortality rate was remarkably higher in Eastern countries (4.1%) than in Western countries (1.0%) ( P <0.01). 3,224 participants (37% female, median age 48 years) were included in our multi-center cohort study, and the proportion of HTG-AP was much higher at 35.9% with a nearly three-fold higher mortality rate compared with acute pancreatitis (AP) due to other etiologies (odds ratio (OR): 2.77, 95% confidence interval (CI): 1.60 to 4.81). The proportion of patients with HTG-AP is remarkably higher in Eastern countries, particularly China, than in Western countries. Furthermore, compared with other causes of AP, HTG-AP has a poorer prognosis and may warrant aggressive management.

Finite element modeling of the biomechanical properties of Populus tomentosa branches and analysis of pruning mechanisms - Yichen Ban; Yang Liu; Shihong Ba; Kun Lyu; Jian Wen; Xiaopeng Bai; Wenbin Li (Computers and Electronics in Agriculture, 2025)

Perfluorooctane sulfonate (PFOS) promotes transformational transfer of antibiotic resistance genes and cross-resistance between antibiotics and PFOS - Hui Zhao; Hai-Ming Zhao; Feng Wu; Bai-Lin Liu; Hui Li; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; Ce Hui Mo; Qing X. Li (Water Research, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Efficiency removal and mechanism of xanthate from flotation tailings wastewater via simulated acid mine drainage (AMD) activate H2O2 oxidization - Xiang Gong; Suqi Li; Xiulan Guo; Jiaqiao Yuan; Hongyu Lu; Shuming Wen; Pan Yu; Shaojun Bai; Dandan Wu (Journal of Water Process Engineering, 2025)

The chlorine migration routes and transformation mechanism during the co-pyrolysis of polyvinyl chloride and low-rank coal - Wang Li; Juan Chen; Zongqing Bai; Yu Wang; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Journal of Cleaner Production, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Spatial variations of PM2.5-bound parent, nitrated, and oxygenated PAHs at urban and suburban sites in the Ili River Valley: Characteristics, sources, and health risks - Xueyan Zhao; Yaqin Ji; Wenyu Bai; Liyao Guo; Chao Gu; Handong Liang; Xianqing Li; Wen Yang (Journal of Environmental Sciences, 2025)

Foodborne outbreak of enterotoxigenic Staphylococcus aureus at a school in Hebei, China - Xiaoyu Zheng; Shengnan Liang; Liang Wen; Hui Wang; Yuchao Bai; Yang Wang; Luyao Cao; Dingchen Li; Jinpeng Guo; Yong Chen; Changjun Wang; Xiong Liu; et al. (Food Research International, 2025)

Fe atom-substituted molybdenum carbide catalyst for the chemoselective hydrogenation of nitro compounds under mild conditions - Hao Wen; Haoyang Li; Weiwei Bai; Huibin Ge; Ruiyang Qu; Hepeng Zhang; Yueling Cao (Chemical Engineering Journal, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

Linaggrenoids A−I, structurally diverse lindenane sesquiterpenoids with anti-hepatic fibrosis effects from Lindera aggregata - Wen-Xian Li; Lu Gan; Yi-Ling Liao; Yu-Wei Wu; Bai-Hui Zhang; De-an Guo; Wei Li (Phytochemistry, 2025)

Insights into norfloxacin biodegradation and the fate of antibiotics resistance genes associated with sulfur-driven autotrophic denitrification - Jin Qian; Sai Bai; Xiaohui Mi; Qi Li; Wen Hao; Yichu Zhang; Xiangjun Pei (Chemical Engineering Journal, 2025)

One-pot green synthesis of liquid crystal polycarbonate towards mechanical robustness, superior fire safety, and efficient closed-loop chemical recycling - Zi-Ni Wang; Xiang-Xin Xiao; Yue Gong; Tong-Yu Bai; Jun-Hao Bai; Hai-Bo Zhao; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Optimization of the injection-production process of underground gas storage in depleted gas reservoir - Haibin Chang; Tangkun Duo; Bei Li; Kai Wen; Tao Meng; Chenbing Bai; Hongwei Zhang (Gas Science and Engineering, 2025)

Bridging the mercury exposure threshold: Development and application of whole-cell biosensors incorporating biotransformation pathways - Xue-ying Liu; Yan Guo; Wen-qi Zhang; Jiao Bai; Bing-chan Ma; Li-ting Zhou; Chang-ye Hui (Environmental Research, 2025)

Flexural behaviors of GFRP-reinforced Engineered Cementitious Composite (ECC)-concrete composite beams - Li-Hui Wang; Wen-Hao Shi; Lan-Ping Qian; Yu-Lei Bai; Shi-Zhu Liu; Zhan-Qun Yang (Engineering Structures, 2025)

Vesicular-like manganese single-atom doped Poly(1,5-Naphthalenediamine) cathode for durable bipolar zinc-organic batteries - Wen Li; Mengying Xu; Leizhou Xu; Li Liu; Peng Wang; Tianwen Bai; Yuju Chen; Qingmao Long; Guanben Du; Lianpeng Zhang (Chemical Engineering Journal, 2025)

Proteome profiling of the lung tissues of the mice co-infected with H9N2 influenza A virus and Pseudomonas aeruginosa - Sun Ying-Li; Fan Hua; Li Wen-qian; Li Dan; Bai Ke-fei; Dong Lu-jiao; Zhang Hui-ning; Li Jian-liang; Xie Zhi-jing (Veterinary Microbiology, 2025)

Construction of the relationship between phytochemicals and gene expression in different Chaenomeles speciosa (Sweet) Nakai cultivars - Ya-Fang Shang; Jun-Hao Miao; Jia Zeng; Si-Qi Sun; Xiao-Long Ni; Zhao-Jun Wei; Yi-Long Ma; Hong-Xing Su; Wen-Bo Bai; Xiang-Li Niu; Wan Zhang (South African Journal of Botany, 2025)

The insight into the fusion process and sintering behaviour of blended ash from co-gasification of coal and biomass feedstock - Zhixin Feng; Jin Bai; Stanislav V. Vassilev; Huaizhu Li; Hao Lu; Zongshuai Yuan; Lingxue Kong; Zhenxing Guo; Zongqing Bai; Wen Li (Fuel, 2025)

Study on the characteristics and role of the soluble fractions during direct liquefaction in two low-rank coals. Part II: Characteristics and thermal behavior of extraction residues - Juan Chen; Wang Li; Zongqing Bai; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Fuel, 2025)

Development of a shear strengthening conductive hydrogel for impact protection and distress signal emission - Juan Tan; Xi Li; Chuan Ru Zheng; Anna Tan; Xiu Chen Li; Hai Liang Ni; Wen Hao Yu; Yue Feng Bai; Ping Hu; Hong Mei Chen (Chemical Engineering Journal, 2025)

Effects of organic material addition on carbon cycling and soil fertility in paddy soil - Nan Zhang; Lingyu Bai; Xiaxing Wei; Tao Li; Yuefeng Tang; Jiong Wen; Zhi Peng; Yang Zhang; Yanan Wang; Xibai Zeng; Shiming Su (Journal of Environmental Management, 2025)

Oxidative pyrolysis characteristics and exothermic heat release effects of cellulose, hemicellulose, and lignin - Jian Li; Wen Fu; Xiaowei Bai; Xiangrui Lin; Heping Yang; Mengfei Wang; Guangxuan Liu; Zhenghua Dai (Fuel, 2025)

Investigation on the synergistic effects and thermokinetic analyses during co-combustion of corn stalk and polyethylene plastic: Effect of heating rate and placement method - Mengjie Liu; Bin Han; Jin Bai; Jiayao Ru; Xuetao Wang; Lili Xing; Haojie Li; Siyu Lv; Aopeng Gao; Yiming Wang; Lingxue Kong; Zongqing Bai; et al. (Fuel, 2025)

S-scheme heterojunction of WO3/metal-covalent organic frameworks for artificial photosynthetic CO2 reduction - Liang Fang; Li-Wen Bai; Di Wu; Hong-Tu Che; Yanxia Jiang; Ya Wang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2025)

Promoted decomposition in straw return to double-cropped rice fields controls soil acidity, increases soil fertility and improves rice yield - Nan Zhang; Lingyu Bai; Xiaxing Wei; Tao Li; Yuefeng Tang; Xibai Zeng; Zhongfang Lei; Jiong Wen; Shiming Su (Chemical Engineering Journal, 2025)

Numerical simulation of strong seismic response of single-layer cylindrical lattice shell considering infill wall effects - Gui-bo Nie; Yu-jie Shi; Wen Bai; Yu-zhu Shang; Hui Li; Zhi-nan Xie; Xu-dong Zhi (Bulletin of Earthquake Engineering, 2025)

The antinociceptive and anti-alpha-glucosidase effects of glucosides from Hemiphragma heterophyllum Wall. - Chun-Fang Wen; Yu-Xiao Li; Ke-Xin Nie; Qiu He; Ya Lu; Zi-Liang Wang; Xi-Shan Bai; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2025)

Dietary supplementation of Litsea cubeba oil promotes growth and intestinal immunity in GIFT tilapia - Fu-Yan Chen; Ying Bai; Gan Yang; Han-Jing Yan; Liu-Yang Li; Zhi-Mou Liu; Ju-Ping Wen; Zhen-Bin Wang; Jun-Hong Xia; Meng-Ling He (Aquaculture, 2025)

Environmental factors ultraviolet a and ozone exacerbate the repeated inhalation toxicity of 6PPD in mice via accelerating the aging reaction - Xianjie Li; Caixia Wu; Ping Yang; Yanxi Li; Shuai Wang; Dan Cai; Ran Wei; Jinfeng Gao; Xuemei Wen; Jieping Luo; Rui Wang; Xueyuan Bai; et al. (Journal of Hazardous Materials, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

Isolation and purification of polyphenols, hypoglycemic and hypolipidemic and active constituent analysis of walnut septum polyphenols - Jing Xie; Li Zhang; Yu-Ying Bai; Wen-Jing Wang; Xia Hu; Shijun Li; Yang Tian (Food Chemistry, 2025)

Enhancing long-term prediction of non-homogeneous landslides incorporating spatiotemporal graph convolutional networks and InSAR - Zongzheng Li; Jianping Chen; Chen Cao; Wen Zhang; Kuanxing Zhu; Ji Bai; Chenyang Wu (Engineering Geology, 2025)

Modelling the size distribution and bioaccumulation of gold nanoparticles under mixture exposure - Yao Li; Xiangrui Wang; Dingyuan Liang; Xiaoli Zhao; Zhaomin Dong; Yingchen Bai; Wen-Xiong Wang; Willie J.G.M. Peijnenburg; Ying Wang; Wenhong Fan (Aquatic Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Gravity anomalies and deep structure of the northeastern Tibetan Plateau and adjacent areas - Guoming Gao; Guofa Kang; Chunhua Bai; Limin Wen; Zaijiao Wang; Yecheng Li (Journal of Asian Earth Sciences, 2025)

Key function mechanism of Na3PO4-modified NaX for enhanced performance and stability in side chain alkylation of toluene with methanol: DFT and experimental perspectives - Faraz Ahmad; Yueli Wen; Muhammad Zeeshan; Bin Wang; Awais Ashraf; Bai Hui; Zheng Cui; Chengda Li; Samia Kausar; Wei Huang (Fuel, 2025)

The dissolution behavior of anorthite in partly crystallized slag of solid fuel at increasing temperature - Hao Lu; Jin Bai; Guixuan Wu; Lingxue Kong; Huaizhu Li; Yu Wang; Zhenxing Guo; Zongqing Bai; Wen Li (Chemical Engineering Journal, 2025)

Membrane transport engineering for efficient yeast biomanufacturing - Xin-Yue Li; Ming-Hai Zhou; Du-Wen Zeng; Yi-Fan Zhu; Feng-Li Zhang; Sha Liao; Ya-Chao Fan; Xin-Qing Zhao; Lin Zhang; Feng-Wu Bai (Bioresource Technology, 2025)

SaTDT enhanced plant tolerance to NaCl stress by modulating the levels of malic acid and citric acid in cells - Xiangyu Wei; Li Xu; Suisui Dong; Nina He; Qianqian Xi; Dan Yao; Qianqian Wang; Yue Zuo; Chen Ling; Meiting Qi; Wen Bai; Kai Han; et al. (Plant Molecular Biology, 2025)

Quaternized and boronic acid dual-functional CoAg nanozymes for label-free, stable, sensitive, and rapid quantitation detection of the bacterial total concentration - Bin Deng; Shao-Bo Li; Jing-Wen Chen; Fang Liu; Jing Liu; Ji Zhou; Zhong-Kai Zhou; Zai-Tian Wang; Li Li; Zong-Chun Bai; Meng-Xiang Su (Analytica Chimica Acta, 2025)

Zinc Combined with Metformin Corrects Zinc Homeostasis and Improves Steroid Synthesis and Semen Quality in Male Type 2 Diabetic Mice by Activating PI3K/AKT/mTOR Pathway - Huanhuan Li; Menghui Zhang; Jing Ma; Wen Li; Xuan Liu; Yuanjing Li; Jiaoying Ma; Dan Yang; Yanqing Tie; Hongzhong Bai; Shusong Wang (Biological Trace Element Research, 2025)

Characteristic analysis of seismic wave propagation at the free surface under the second-order strain gradient theory - Chao-pu Chen; Wen-lei Bai; Hong Liu; You-ming Li; Zhi-yang Wang (Applied Geophysics, 2025)

In-situ constructing 3D nanocarbon conduction conformal network on silicon anodes for high-performance sulfide-based all-solid-state batteries - Rui Huang; Ruilong Li; Shaobo Li; Wen Yang; Yu Bai; Zhenhua Wang; Kening Sun (Chemical Engineering Journal, 2025)

Flotation separation of ilmenite and titanaugite by sodium oleate (NaOL)/cetyltrimethylammonium bromide (CTAB) mixed collectors: Selectivity and synergistic adsorption mechanism - Jiaqiao Yuan; Yijie Zhang; Anmei Yu; Li Chen; Shuming Wen; Shaojun Bai (Journal of Environmental Chemical Engineering, 2024)

Umami-enhancing effect of Agaricus bisporus-pork bone stocks based on the EUC value and sensory evaluation - Ke Shi; Zhenqi Li; Yibo Bai; Yu Zhang; Huanlu Song; Wenqing Pan; Wanying Chen; Wen Xiong; Li Yang; Zijian Huang (International Journal of Gastronomy and Food Science, 2024)

Immobilization of heavy metals with chlorine and liquid phase formation during thermal treatment of MSWI fly ash - Zongshuai Yuan; Qinchao Xu; Xiaodong Chen; Lingxue Kong; Kaifeng Li; Chuang Wu; Jin Bai; Jinjun Guo; Zhenxing Guo; Zongqing Bai; Huaizhu Li; Wen Li (Fuel, 2024)

Protein/polysaccharide based oral delivery system for precise targeting of polyphenols and carotenoids - Wen Jiang; Shiyu Zhai; Li Zhu; Yanan Bai; Jianuo Li; Juxiu Li (Food Bioscience, 2024)

Benzobisoxazole-based covalent organic frameworks for efficient photocatalytic oxidation - Wen Wang; Yuhongxu Bai; Zhongliang Li; Qing Su; Boai Li; Meng Lei; Jing Feng; Ao Xu; Qiaolin Wu (Chemical Engineering Journal, 2024)

Impact of anthropogenic and natural constituents on particulate matter in oasis cities on the southern margin of the Taklimakan Desert based on MERRA-2 and multi-site ground observation - Hao Yu; Jing Wang; Chunmei Geng; Wen Yang; Xinhua Wang; Baohui Yin; Chao Gu; Shuang Gao; Li Chen; Zhipeng Bai (Atmospheric Research, 2024)

A biobank of patient derived glioma organoids - Yulin Wen; Hongmin Bai; Qing Li; Sainan Huang; Xiaokun Jia; Guangjin Pan; Hongjie Yao (Science China Life Sciences, 2024)

Rapamycin protects mouse skin from ultraviolet B-induced photodamage by modulating Hspb2-mediated autophagy and apoptosis - Ang Li; Ai-Jun Chen; Jing Xu; Zhu-Yuan Wen; Gen-Long Bai; Zi-Yue Wang; Yu-Xin Jiang; Ping Wang (Molecular Biology Reports, 2024)

Association Between Neuroinflammation and Parkinson’s Disease: A Comprehensive Mendelian Randomization Study - YiNi Wang; XinYu Shi; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Bai-Xiang Li; Kun Ma (Molecular Neurobiology, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Characterization and origin of high-Al chromitites: A case study of chromite deposit in the Kudi ophiolite in the NW Tibetan Plateau - Jian-Guo Liu; Ben-Xun Su; Xia Liu; Wen-Jun Li; Yang Bai; Jian Wang; Xiang-Jie Wen; Shi-Chun Li (Lithos, 2024)

Immobilization mechanism of heavy metals by crystals and liquid phase during melting treatment of MSWI fly ash - Zongshuai Yuan; Guangkai Cai; Lingxue Kong; Min Wu; Jin Bai; Zongqing Bai; Huaizhu Li; Wen Li (Journal of Environmental Management, 2024)

Study on the co-pyrolysis interactions and chlorine migration behaviors of polyvinyl chloride and Hami coal - Wang Li; Juan Chen; Zongqing Bai; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Fuel, 2024)

A molecular mechanism underlies grass carp (Ctenopharyngodon idella) TARBP2 regulating PKR-mediated cell apoptosis - Miao-miao Li; Chang-bai Tao; Mei-feng Li; Chu-xin Wu; Ting-ting Yu; Zhi-qing Feng; Qing-Zhang; Ze-yin Jiang; Hui-ling Mao; Shang-hong Wang; Xiao-wen Xu; Cheng-yu Hu (Fish & Shellfish Immunology, 2024)

Lipoic acid-functionalized platycodin D nanocarrier improves mitochondrial dysfunction and reverses diabetes - Qiong Shen; Wen-Ting Wang; Qiao-Yue Xing; Yan Bai; Yan-Fei Li (Chemical Engineering Journal, 2024)

Accurately estimate soybean growth stages from UAV imagery by accounting for spatial heterogeneity and climate factors across multiple environments - Yingpu Che; Yongzhe Gu; Dong Bai; Delin Li; Jindong Li; Chaosen Zhao; Qiang Wang; Hongmei Qiu; Wen Huang; Chunyan Yang; Qingsong Zhao; Like Liu; et al. (Computers and Electronics in Agriculture, 2024)

The resistance mechanism of humic acids and proteins in soluble microbial products from activated sludge against silver nanoparticles - Jia Kang; Yi-hang Wang; Yao-wen Zhang; Chu-qiong Song; Ao-di Wang; Ning Zhou; Yi-hui Zhang; Fa-zhan Li; Shu-li Liu; Li-sha Liu; Gang-fu Song; Bai-hong Wang (Journal of Environmental Chemical Engineering, 2024)

Thermomechanical and thermodynamic analysis of the sintering process of Mn-based oxygen carrier in chemical looping gasification of biomass - Xiaoming Li; Shiyin Feng; Yujun Guo; Chong He; Huaizhu Li; Jin Bai; Wen Li (Fuel, 2024)

Discovery of anti-melanogenic components in persimmon (Diospyros kaki) leaf using LC-MS/MS-MN, AlphaFold2-enabled virtual screening and biological validation - Jiazheng Liu; Ting Xu; Jianjun Ding; Haoyue Wen; Jieru Meng; Qing Liu; Xiaomei Liu; Wei Zhang; Guo-Yuan Zhu; Zhi-Hong Jiang; Jin Gao; Li-Ping Bai (Food Chemistry, 2024)

Generation and Characterization of Induced Pluripotent Stem Cells Carrying An ASXL1 Mutation - Wenjun Wang; Xiaoru Zhang; Yunan Li; Jun Shen; Yihan Li; Wen Xing; Jie Bai; Jun Shi; Yuan Zhou (Stem Cell Reviews and Reports, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Carbon isotope geochemistry and its geological significance in the Jixian system of the Qishan section, Ordos Basin - Qian Zhang; Wenhui Liu; Wen Zhang; Haifeng Bai; Wenhou Li; Zhaoyu Li; Fengjiao Li; Mengyu Xie; Jiayu Zhang; Fuqi Li; Xiaofeng Wang; Dongdong Zhang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Mining flotation reagents: Quantitative and robust analysis of metal-xanthate complexes in water - Wen-Jun Wu; Qing-Jun Zheng; Jing-Wen Liang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Nai-Xian Feng; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Study on the characteristics and role of the soluble fractions during direct liquefaction for two low rank coals. Part I: Structural comparison between the soluble fractions obtained from soxhlet and thermal extraction - Juan Chen; Zongqing Bai; Hongyan Zheng; Wang Li; Tingting Zhang; Yuxing Jia; Yujie Hou; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Fuel, 2024)

Catalytic upgrading of Hami coal pyrolysis volatiles over mesoporous kaolin prepared by calcination and NaOH leaching - Yujie Hou; Hao Lu; Zongqing Bai; Hongyan Zheng; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Fuel, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Biomolecular condensates and disease pathogenesis - Ke Ruan; Ge Bai; Yanshan Fang; Dan Li; Tingting Li; Xingguo Liu; Boxun Lu; Qing Lu; Zhou Songyang; Shuguo Sun; Zheng Wang; Xin Zhang; et al. (Science China Life Sciences, 2024)

Analysis of the Relationship Between Parkinson’s Disease and Diabetic Retinopathy Based on Bioinformatics Methods - XinYu Shi; YiNi Wang; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Kun Ma; Bai-Xiang Li (Molecular Neurobiology, 2024)

A Hybrid Dung Beetle Optimization Algorithm with Simulated Annealing for the Numerical Modeling of Asymmetric Wave Equations - Xu-ruo Wei; Wen-lei Bai; Lu Liu; You-ming Li; Zhi-yang Wang (Applied Geophysics, 2024)

Tailoring metal-support interactions via spatial confinement of Ni/CeO2 interfaces on h-BN for efficient CO2 methanation - Shuangxi Lin; Longchen Gong; Ning Zhao; Huibo Zhao; Feigang Zhao; Yang Bai; Zhenhua Li; Wen Liu (Chemical Engineering Journal, 2024)

Sources, trigger points, and effect size of associations between PM2.5-bound polycyclic aromatic hydrocarbons (PAHs) and fractional exhaled nitric oxide (FeNO): A panel study with 16 follow-up visits over 4 years - Yucong Fu; Wenhui Jia; Ningyu Zhang; Zhiyu Wang; Nan Zhang; Tong Wang; Nan Zhang; Jia Xu; Xueli Yang; Qiang Zhang; Changping Li; Xumei Zhang; et al. (Chemosphere, 2024)

Simultaneous methane mitigation and nitrogen removal by denitrifying anaerobic methane oxidation in lake sediments - Yanan Bai; Wangting Yang; Hanyu Li; Qinan Hu; Sile Wen; Lidong Shen; Yuzhi Song (Science of The Total Environment, 2024)

Catalytic hydroconversion of aryl ethers to polycyclic alkanes over Ni@MCM-41/β composite zeolite: Aromatic α-carbon activation and hydrogen transfer mechanisms - Guang-Hui Liu; Wen-Ao Shi; Jun Li; Han Wang; Ai-Min Wang; Yu-Hong Kang; Yong Gao; Ni Bai; Jie Kang; Chen Shi; Xian-Yong Wei (Fuel, 2024)

Inverse analysis of geotechnical parameters using an improved version of non-dominated sorting genetic algorithm II - Bo-Hu He; Xiu-Li Du; Ming-Zhou Bai; Jin-Wen Yang; Dong Ma (Computers and Geotechnics, 2024)

Realizing high-efficiency thermoelectric module by suppressing donor-like effect and improving preferred orientation in n-type Bi2(Te, Se)3 - Yichen Li; Shulin Bai; Yi Wen; Zhe Zhao; Lei Wang; Shibo Liu; Junqing Zheng; Siqi Wang; Shan Liu; Dezheng Gao; Dongrui Liu; Yingcai Zhu; et al. (Science Bulletin, 2024)

Piezocatalytically-induced controllable mineralization scaffold with bone-like microenvironment to achieve endogenous bone regeneration - Xi Cui; Lingling Xu; Yizhu Shan; Jiaxuan Li; Jianying Ji; Engui Wang; Baokun Zhang; Xiaozhou Wen; Yuan Bai; Dan Luo; Chunying Chen; Zhou Li (Science Bulletin, 2024)

Formation conditions of Jixian System cherts in the Qishan area, Ordos Basin: Implications for marine redox conditions and paleoecology - Qian Zhang; Wenhui Liu; Wen Zhang; Haifeng Bai; Zhaoyu Li; Xiaofeng Wang; Dongdong Zhang; Xiaoyan Chen; Wenhou Li (Sedimentary Geology, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Recent advances in the authentication (geographical origins, varieties and aging time) of tangerine peel (Citri reticulatae pericarpium): A review - Yanxin Li; Wenhong Zhao; Min Qian; Zhiyi Wen; Weidong Bai; Xiaofang Zeng; Hong Wang; Yanping Xian; Hao Dong (Food Chemistry, 2024)

Digital Twin-Based Pump Station Dynamic Scheduling for Energy-Saving Optimization in Water Supply System - Sheng-Wen Zhou; Shun-Sheng Guo; Wen-Xiang Xu; Bai-Gang Du; Jun-Yong Liang; Lei Wang; Yi-Bing Li (Water Resources Management, 2024)

Subregions of the fusiform gyrus are differentially involved in the attentional mechanism supporting visual mental imagery in depression - Jun-He Zhou; Bin-Kun Huang; Di Wang; Bai-Le Ning; Xue-Song Liang; Chang-Hong Li; Zeng-Jian Wang; Ying Deng; Xi-Chang Huang; De-Long Zhang; Wen-Bin Fu (Brain Imaging and Behavior, 2024)

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

Asiaticasics A-O, structurally intriguing coumarins from Toddalia asiatica with potential inflammatory inhibitory activity - Si-Chen Song; Bai-Dong Ren; Xue-Wen Wu; Yi-Fan Xie; Bin Cheng; Qiong Wei; Wen-Hui Pang; Ze-Kai Wu; Xing-Jie Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Corrigendum to “Optimization of briquetting conditions and influencing factors of high-strength sludge briquette” [J. Clean. Prod. 432 (2023) 139749] - Peilong Gao; Zongqing Bai; Tingting Zhang; Yuxing Jia; Yujie Hou; Wang Li; Juan Chen; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Journal of Cleaner Production, 2024)

Identification of particle distribution pattern in vertical profile via unmanned aerial vehicles observation - Zhi-Heng Chen; Bo-Wen Li; Bai Li; Zhong-Ren Peng; Hai-Chao Huang; Jun-Qi Wu; Hong-Di He (Environmental Pollution, 2024)

β-Glucuronidase-triggered reaction for fluorometric and colorimetric dual-mode assay based on the in situ formation of silicon nanoparticles - Yue Li; Weiping Liu; Xinxin Jiang; Hongmei Liu; Sikai Wang; Xiaoqian Mao; Ruyu Bai; Yulu Wen; Xiaojun Luo; Guoqi Zhang; Yan Zhao (Analytica Chimica Acta, 2024)

Two new monoterpene esters from Illigera paviflora Dunn roots - Meng-Yuan Jiang; Xiao-Yun Pu; Wen-Ting Li; Juan Liu; Xiao-Li Zeng; Hong-Rui Li; Xi-Shan Bai; Lin Hu; Xiang-Zhong Huang (Natural Product Research, 2024)

Changes of characteristics and disinfection by-products formation potential of intracellular organic matter with different molecular weight in metalimnetic oxygen minimum - Yuannan Bai; Kai Li; Ruihua Cao; Huining Xu; Jingyi Wang; Tinglin Huang; Gang Wen (Chemosphere, 2024)

Cevanine-type alkaloids from the bulbs of Fritillaria unibracteata var. wabuensis and their antifibrotic activities in vitro - Lu Fu; Wenyue Tian; Meng-Yu Bao; Zhiyan Liu; Wen-Jing Ren; Jiazheng Liu; Wei Zhang; Zhifeng Zhang; Jin Gao; Li-Ping Bai; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2024)

The kinetic characteristics of mullite crystallization in slag with high SiO2 and Al2O3 content at gasification condition of solid fuel - Kaifeng Li; Hao Lu; Zongshuai Yuan; Haoyu Dou; Jin Bai; Lingxue Kong; Huaizhu Li; Zhenxing Guo; Zongqing Bai; Wen Li (Fuel, 2024)

Multi-period early-warning precipitation identification method for the easily waterlogged districts in Jiangxi province, China - Hua Bai; Bingxiang Wang; Bin Li; Zhangjun Liu; Zhenyu Wen; Yang Zhang; Feng Xiao; Xinfa Xu; Yongfeng Huang (Theoretical and Applied Climatology, 2024)

Industrial fluoride emissions and their spatial characteristics in the Nansi Lake Basin, Eastern China - Dandan Liu; Xueying Li; Yue Zhang; Lu Bai; Huijian Shi; Qi Qiao; Tianran Li; Wen Xu; Xiaoyun Zhou; Hejing Wang (Environmental Science and Pollution Research, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Co-pyrolysis of Hami coal and mixed plastic: An interaction between primary volatiles study via in-situ Py-TOF-MS - Tingting Zhang; Zongqing Bai; Hongyan Zheng; Haoyu Dou; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Fuel, 2024)

Machine learning-assisted design and scalable fabrication of high-performance fire-safe polycarbonate for advanced applications - Xiang-Xin Xiao; Tong-Yu Bai; Qin Zhang; Zi-Xun Chen; Zi-Ni Wang; Jun-Hao Bai; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Rheb1 is required for limb growth through regulating chondrogenesis in growth plate - Yuwei Zhang; Jiaxin Wen; Ruijun Lai; Jiahuan Zhang; Kai Li; Yue Zhang; Anling Liu; Xiaochun Bai (Cell and Tissue Research, 2024)
Ras homology enriched in the brain (Rheb) is well established as a critical regulator of cell proliferation and differentiation in response to growth factors and nutrients. However, the role of Rheb1 in limb development remains unknown. Here, we found that Rheb1 was dynamically expressed during the proliferation and differentiation of chondrocytes in the growth plate. Given that Prrx1 + limb-bud-like mesenchymal cells are the source of limb chondrocytes and are essential for endochondral ossification, we conditionally deleted Rheb1 using Prrx1-Cre and found a limb dwarfism in Prrx1-Cre; Rheb1 fl/fl mice. Normalized to growth plate height, the conditional knockout (cKO) mice exhibited a significant decrease in column count of proliferative zones which was increased in hypertrophic zones resulting in decreased growth plate size, indicating abnormal endochondral ossification. Interestingly, although Rheb1 deletion profoundly inhibited the transcription factor Sox9 in limb cartilage; levels of runx2 and collagen type 2 were both increased. These novel findings highlight the essential role of Rheb1 in limb growth and indicate a complex regulation of Rheb1 in chondrocyte proliferation and differentiation.

Ambient PM2.5-bound polycyclic aromatic hydrocarbons (PAHs) associated with pro-thrombotic biomarkers among young healthy adults: A 16 times repeated measurements panel study - Wenhui Jia; Yucong Fu; Nan Zhang; Ningyu Zhang; Tong Wang; Zhiyu Wang; Nan Zhang; Jia Xu; Xueli Yang; Qiang Zhang; Changping Li; Xumei Zhang; et al. (Science of The Total Environment, 2024)

Effect of SiO2/CaO on the viscosity and structure of yellow phosphorus slag in the electric furnace - Zhibin Lu; Jin Bai; Lingxue Kong; Huaizhu Li; Zhenxing Guo; Zongqing Bai; Wen Li (Fuel, 2024)

A new viscosity model for the high-iron coal slag based on the bond distribution - Jing Guo; Chong He; Jin Bai; Xiaoming Li; Wen Li (Fuel, 2024)

Effect of chromium on the spatial distribution of sulfur during pyrolysis of coal with high organic sulfur - Yuxing Jia; Zongqing Bai; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Fuel, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

An innovative method to degrade xanthate from flotation tailings wastewater in acid mine drainage (AMD) system: Performance, degradation mechanism and pathways - Jiaqiao Yuan; Zhan Ding; Jie Li; Anmei Yu; Shuming Wen; Shaojun Bai (Journal of Environmental Management, 2024)

Anthocyanins degradation mediated by β-glycosidase contributes to the color loss during alcoholic fermentation in a structure-dependent manner - Kailan Yuan; Guangkai Wu; Xusheng Li; Yingyu Zeng; Xinyuan Wen; Ruijing Liu; Xinwei Jiang; Lingmin Tian; Jianxia Sun; Weibin Bai (Food Research International, 2024)

Feeding strategy determine flexible biogas via shaping microbial abundance and interaction in anaerobic digestion - Pengjie Wu; Tianyu Bai; Ying Yang; Kunyao Li; Hao Tan; Suyu Zhuang; Fuyu Song; Zuopeng Lv; Hongyu Wen; Haiying Yu (Biomass and Bioenergy, 2024)

An insight into the health beneficial of probiotics dairy products: a critical review - JinTao He; Wen Li; Jing Deng; QinLu Lin; Jie Bai; Lin Zhang; Yong Fang (Critical Reviews in Food Science and Nutrition, 2023)

Unveiling the traits of dry and wet pre-magnetized zero-valent iron-activated peroxymonosulfate: Degradation of oxytetracycline - Yang Wu; Jia-wen Bai; Jing-ying Zhu; Zhi-hao Li; Yi-fan Shao; Qing-qing Xiao (Chemosphere, 2023)

Characterization and biocontrol mechanism of Streptomyces olivoreticuli as a potential biocontrol agent against Rhizoctonia solani - Jie Zhong; Wen Wen Sui; Xin Yi Bai; Ze Lan Qiu; Xiao Gang Li; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2023)

Insights into the influence of calcium ions on the adsorption behavior of sodium oleate and its response to flotation of quartz: FT-IR, XPS and AMF studies - Zhan Ding; Jie Li; Jiaqiao Yuan; Anmei Yu; Shuming Wen; Shaojun Bai (Minerals Engineering, 2023)

Optimization of briquetting conditions and influencing factors of high-strength sludge briquette - Peilong Gao; Zongqing Bai; Tingting Zhang; Yuxing Jia; Yujie Hou; Wang Li; Juan Chen; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Journal of Cleaner Production, 2023)

Investigation on the catalytic performance of magnetic copper ferrite nanoparticles in the catalytic hydroconversion of Hanglaiwan long flame coal - Yong Gao; Wen-Xian Qin; Jin-Jun Bai; Qi-Yang Zhu; Xia-Long Li; Guang-Hui Liu; Xian-Yong Wei; Yu-Hong Kang; Yan-Jun Li; Xiang-Rong Ma; Zhi-Min Zong (Fuel, 2023)

Study on the mechanism of the influence of surfactant alkyl chain length on the wettability of anthracite dust based on EDLVO theory and inverse gas chromatography - Xuyang Bai; Guochao Yan; Shaoqi Kong; Tao Yang; Jia Yao; Pengcheng Wen; Gang Li (Fuel, 2023)

Correlations between flavor and fermentation days and changes in quality-related physiochemical characteristics of fermented Aurantii Fructus - Ya-Ting Xie; Ting-Ting Bai; Tao Zhang; Peng Zheng; Min Huang; Li Xin; Wen-Hui Gong; Abid Naeem; Fang-You Chen; Hua Zhang; Jin-Lian Zhang (Food Chemistry, 2023)

The crystallization kinetics analysis and the new prediction index of melilite-bearing slag under solid fuel gasification condition - Hao Lu; Jin Bai; Lingxue Kong; Huaizhu Li; Zongqing Bai; Wen Li (Chemical Engineering Journal, 2023)

Scene-aware refinement network for unsupervised monocular depth estimation in ultra-low altitude oblique photography of UAV - Kailong Yu; Hao Li; Linjie Xing; Tao Wen; Die Fu; Yang Yang; Chengjiang Zhou; Rong Chang; Shan Zhao; Lin Xing; Haicheng Bai (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Heterogeneous oxidative desulfurization of fuels using amphiphilic mesoporous phosphomolybdate-based poly(ionic liquid) over a wide temperature range - Shao-Xu Mao; Jun-Yi Song; Wen-Shuai Zhu; Hua-Ming Li; Jing-Yu Pang; Dong-Bin Dang; Yan Bai (Fuel, 2023)

A large and overlooked Cd source in karst areas: The migration and origin of Cd during soil formation and erosion - Xiao Wei; Xiaoyong Bai; Xuefeng Wen; Li Liu; Jie Xiong; Changlong Yang (Science of The Total Environment, 2023)

Excessive N applications reduces yield and biological N fixation of summer-peanut in the North China Plain - Wenhai Huang; Yuhao Yang; Haoyu Zheng; Jørgen Eivind Olesen; Robert M. Rees; Jun Zou; Li Zhang; Suya Hu; Bowen Qiao; Xiaohui Wang; Shuaijie Shen; Biaoding Yang; et al. (Field Crops Research, 2023)

Plant-soil interactions in grasslands of the Mongolian Plateau under global change - Wen-Hao Zhang; Long Li; Feike Dijkstra; Biao Zhu; Wenming Bai; Qiuying Tian (Plant and Soil, 2023)

The response of two nutrient acquisition strategies: root traits and leaf nutrient resorption and their relationships to long-term mowing in a temperate steppe - Qingmei Li; Wenming Bai; Yumeng Guo; Jun Sheng; Yujia Yuan; Wen-Hao Zhang; Meng Zhou (Plant and Soil, 2023)

Preemptive QP001, a fast-acting meloxicam formulation, provides analgesia and reduces opioid consumption following abdominal surgery: a randomized controlled trial - Yingyong Zhou; Bin Wang; Kaiming Duan; Zhihong Bai; Xianwen Hu; Mingjun Xu; Xiaohong Li; Yuanli Gao; Jiangang Li; Mengchang Yang; Ying Zhang; Wei Zhang; et al. (Inflammopharmacology, 2023)

Insights into electrogenerated intermediates and rapid screening of electrochemical reactions by surface-modified carbon fiber paper redox spray ionization mass spectrometry - Jiahui Bai; Mingmai Bao; Shanshan Wang; Tianlun Wen; Yuling Li; Jing Zhang; Tiansheng Mei; Yinlong Guo (Analytica Chimica Acta, 2023)

Dynamic structure transformation of char precursors during co-pyrolysis of coal and HDPE by using ReaxFF MD simulation and experiments - Wei Feng; Mo Zheng; Jin Bai; Xianxian Zhang; Chuang Wu; Zhenxing Guo; Lingxue Kong; Zongqing Bai; Wen Li (Chemical Engineering Journal, 2023)

Neuroprotective effect of salidroside on hippocampal neurons in diabetic mice via PI3K/Akt/GSK-3β signaling pathway - Xue-Hua Wang; Zhong-Fu Zuo; Lu Meng; Qi Yang; Pan Lv; Li-Pan Zhao; Xiao-Bai Wang; Yu-Fei Wang; Ying Huang; Cong Fu; Wen-Qiang Liu; Xue-Zheng Liu; et al. (Psychopharmacology, 2023)

LINC02870 facilitates SNAIL translation to promote hepatocellular carcinoma progression - Mengya Guo; Hao Zhuang; Jianing Huang; Xiaowen Shao; Nan Bai; Minghe Li; Minmin Niu; Wen Wei; Li Sun; Yongmei Li; Zhaoyan Qiang (Molecular and Cellular Biochemistry, 2023)

Neuronal differentiation and functional maturation of neurons from neural stem cells induced by bFGF-chitosan controlled release system - Tianyu Bai; Hongmei Duan; Boya Zhang; Peng Hao; Wen Zhao; Yudan Gao; Zhaoyang Yang; Xiaoguang Li (Drug Delivery and Translational Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Wnt/β-Catenin Promotes the Osteoblastic Potential of BMP9 Through Down-Regulating Cyp26b1 in Mesenchymal Stem Cells - Xin-Tong Yao; Pei-pei Li; Jiang Liu; Yuan-Yuan Yang; Zhen-Ling Luo; Hai-Tao Jiang; Wen-Ge He; Hong-Hong Luo; Yi-Xuan Deng; Bai-Cheng He (Tissue Engineering and Regenerative Medicine, 2023)

The physical encapsulation and chemical fixation of Zn during thermal treatment process of municipal solid waste incineration (MSWI) fly ash - Zongshuai Yuan; Guangkai Cai; Longfei Gao; Min Wu; Lingxue Kong; Jin Bai; Zongqing Bai; Huaizhu Li; Wen Li (Waste Management, 2023)

Potassium isotope fractionation during granite differentiation and implications for crustal K isotope heterogeneity - Zi-Yi Ding; Shan-Ke Liu; Ben-Xun Su; Wen-Jun Li; Yang Bai; Qi-Qi Pan; Fang-Yang Hu; Kwan-Nang Pang (Lithos, 2023)

Identification and characterization of goat milk key flavor compounds and their precursors in electron beam irradiation and pasteurization on raw - Chunlu Wen; Ya Chen; Madina; Linlu Zhang; Yue Peng; Bai Rong; Linjie Xi; Shengqi Jiang; Jiangtao Yu; Junqing Bai; Niu Wei; Li Kui; et al. (Innovative Food Science & Emerging Technologies, 2023)

Suppression of anthracite dust by a composite of oppositely-charged ionic surfactants with ultra-high surface activity: Theoretical calculation and experiments - Xuyang Bai; Guochao Yan; Shaoqi Kong; Jia Yao; Pengcheng Wen; Gang Li; Jiajun Li; Jiawei Zhang (Fuel, 2023)

Investigation of sintering and fusibility of iron-rich coal ashes derived from varied coal mines under air condition - Wenju Shi; Xuemei Wu; Jin Bai; Jingpei Cao; Wen Li (Fuel, 2023)

Comparative study on the effects of heating rate on char gasification behaviors by thermogravimetric analyzer and high-temperature stage microscope under non-isothermal condition - Mengjie Liu; Cheng Zhang; Jin Bai; Xuetao Wang; Lili Xing; Xiaoming Li; Bin Han; Lingxue Kong; Zongqing Bai; Huaizhu Li; Wen Li (Fuel, 2023)

Effect of phosphorus on viscosity-temperature behavior of high-sodium coal ash slag - Xianxian Zhang; Haoyu Dou; Jin Bai; Lingxue Kong; Wei Feng; Huaizhu Li; Zhenxing Guo; Zongqing Bai; Ping Li; Wen Li (Fuel, 2023)

Temporal Process and Leaching Characteristics for Runoff Pollutants in Typical Solid Waste Improved Bioretention Filters - Chunbo Jiang; Xinzhu Peng; Zhenguo Dang; Jiake Li; Wen Dong; Xi Yang; Yangxuan Zhang; Xuerui Bai; Qiang Yang (Water, Air, & Soil Pollution, 2023)

SOV sensitizes gastric cancer cells to radiation by suppressing radiation-induced autophagy in vitro and in vivo - Wen Wang; Xiao-gan Jiang; Ya-ping Bai; Heng Li; Ling-xi Gao; Teng Zhang; Fang-yi Dong; Wen-ping Ding; Yan Zhang (Tissue and Cell, 2023)

Reduction behavior and growth kinetics of metallic iron in slag bath of BGL coal gasifier - Chuang Wu; Hao Lu; Jin Bai; Lingxue Kong; Ji Wang; Lei Huang; Wei Feng; Zongshuai Yuan; Chong He; Zhenxing Guo; Zongqing Bai; Huaizhu Li; et al. (Fuel, 2023)

The critical condition and kinetics of interaction between residual char and slag in the coal slagging gasifier - Ji Wang; Zongshuai Yuan; Lingxue Kong; Huaizhu Li; Jin Bai; Zhiqing Wang; Zongqing Bai; Ping Li; Wen Li (Fuel, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Coconut shell biochar application in liquid-solid microextraction of triazine herbicides from multi-media environmental samples - Mengge Ma; Zongliang Niu; Zhuhua Tang; Jinyang Bai; Bei Li; Yuling Zhou; Yingying Wen (Analytica Chimica Acta, 2023)

Construction of subway station using the small pipe roof-beam method: A case study of Shifu Road station in Shenyang - Qian Bai; Yingda Zhang; Wen Zhao; Pengjiao Jia; Shengang Li; Zhiguo Wang (Tunnelling and Underground Space Technology, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Comparative study on pyrolysis behaviors and chlorine release of pure PVC polymer and commercial PVC plastics - Wang Li; Zongqing Bai; Tingting Zhang; Yuxing Jia; Yujie Hou; Juan Chen; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Fuel, 2023)

Determination of running temperature in entrained flow gasifier in regard to coal ash melting thermal kinetic effects - Wenju Shi; Xuemei Wu; Jin Bai; Lingxue Kong; Xiaoming Li; Jingpei Cao; Wen Li (Fuel, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Flavonoids derived from licorice suppress LPS-induced acute lung injury in mice by inhibiting the cGAS-STING signaling pathway - Jincai Wen; Shuanglin Qin; Yurong Li; Ping Zhang; Xiaoyan Zhan; Mingxia Fang; Ce Shi; Wenqing Mu; Wen Kan; Jia Zhao; Siwen Hui; Manting Hou; et al. (Food and Chemical Toxicology, 2023)

Integrating ambient carbonyl compounds provides insight into the constrained ozone formation chemistry in Zibo city of the North China Plain - Ze Qin; Bo Xu; Zhensen Zheng; Liming Li; Guotao Zhang; Shijie Li; Chunmei Geng; Zhipeng Bai; Wen Yang (Environmental Pollution, 2023)

Synergistic effect of Hami coal and polystyrene on products properties during co-pyrolysis: Evaluation on the contribution of different interaction sources - Tingting Zhang; Zongqing Bai; Zhenxing Guo; Lingxue Kong; Haoyu Dou; Jin Bai; Wen Li (Fuel, 2023)

Halloysite nanotube/black phosphorene nanohybrid modified screen-printed carbon electrode as an ultra-portable electrochemical sensing platform for smartphone-capable detection of maleic hydrazide with machine learning assistance - Yu Ge; Minghui Li; Ying Zhong; Lulu Xu; Xinyu Lu; Jiaqi Hu; Quanming Peng; Ling Bai; Yangping Wen (Food Chemistry, 2023)

The ability of pre-magnetized zero-valent iron for peroxymonosulfate activation to remove ofloxacin - Yang Wu; Jing-ying Zhu; Jia-wen Bai; Li-feng Lin; Chang-ping Yu (Chemical Engineering Journal, 2023)

Transcriptomic and metabolomic profiling reveal the role of BoMYB2 in flavor regulation mechanism and coloration in the postharvest purple cauliflower - Feng Luo; Guo-Bao Niu; Qian Zhou; Li-Jie Wang; Li-Juan Bai; Wen-Zheng Gao (Postharvest Biology and Technology, 2023)

Development of epitopephore-based rational hapten design strategy: A combination of theoretical evidence and experimental validation - Xiya Zhang; Yuchen Bai; Qianqian Tang; Minggang Liu; Li Nan; Kai Wen; Xuezhi Yu; Wenbo Yu; Jianzhong Shen; Zhanhui Wang (Journal of Hazardous Materials, 2023)

Simultaneous determination of dissolved organic nitrogen, nitrite, nitrate and ammonia using size exclusion chromatography coupled with nitrogen detector - Wen-Xiang Ji; Ye-Chao Tian; Min-Hui Cai; Bi-Cun Jiang; Shi Cheng; Yan Li; Qing Zhou; Bo-Qiang Li; Bai-Yang Chen; Xing Zheng; Wen-Tao Li; Ai-Min Li (Journal of Environmental Sciences, 2023)

Insights on the stem elongation of spur-type bud sport mutant of ‘Red Delicious’ apple - Wen-Fang Li; Zong-Huan Ma; Zhi-Gang Guo; Cun-Wu Zuo; Ming-Yu Chu; Juan Mao; Bai-Hong Chen (Planta, 2023)

Neuroplasticity-Related Genes and Dopamine Receptors Associated with Regional Cortical Thickness Increase Following Electroconvulsive Therapy for Major Depressive Disorder - Gong-Jun Ji; Jiao Li; Wei Liao; Yingru Wang; Lei Zhang; Tongjian Bai; Ting Zhang; Wen Xie; Kongliang He; Chuyan Zhu; Juergen Dukart; Chris Baeken; et al. (Molecular Neurobiology, 2023)

Water quality criteria derivation and tiered ecological risk evaluation of antifouling biocides in marine environment - Hai-Wei Luo; Min Lin; Xin-Xin Bai; Bin Xu; Minjie Li; Jin-Jian Ding; Wen-Jun Hong; Liang-Hong Guo (Marine Pollution Bulletin, 2023)

Molecular mechanism of di-n-butyl phthalate promotion of bladder cancer development - En-Hui Li; Bai-Hui Xu; Hai-Bin Wei; Yu-Chen Bai; Qi Zhang; Wei-Wen Yu; Zhi-Hui Xu; Xiao-Long Qi; Da-Hong Zhang; Heng Wang (Toxicology in Vitro, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

A new phragmalin-type limonoid from the roots of Trichilia sinensis - Shou-Bai Liu; Jin-Ling Yang; Hui-Qin Chen; Cheng-min Yang; Hao Wang; Cai-Hong Cai; Jing-Zhe Yuan; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2023)

Insight into the spatial distribution of sulfur during pyrolysis of coal with high organic sulfur - Yuxing Jia; Zongqing Bai; Xin Dai; Ranran Hou; Zhihao Feng; Yujie Hou; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Fuel, 2023)

Porous phosphomolybdate-based poly(ionic liquid) hybrids with reversible water absorption for enhancement of oxidative desulfurization - Shao-Xu Mao; Qi-Hang Zhou; Hui-Li Guo; Ming Du; Wen-Shuai Zhu; Hua-Ming Li; Jing-Yu Pang; Dong-Bin Dang; Yan Bai (Fuel, 2023)

Effect of P2O5 on the viscosity of yellow phosphorus slag in electric furnace at high temperatures - Zhibin Lu; Hao Lu; Lei Huang; Lingxue Kong; Huaizhu Li; Jin Bai; Zhenxing Guo; Zongqing Bai; Wen Li (Fuel, 2023)

The light absorbing and molecule characteristic of PM2.5 brown carbon observed in urban Shanghai - Zhe Bai; Wen Wen; Wei Zhang; Ling Li; Lina Wang; Jianmin Chen (Environmental Pollution, 2023)

Investigation of O3-precursor relationship nearby oil fields of Shandong, China - Liming Li; Zhensen Zheng; Bo Xu; Xinhua Wang; Zhipeng Bai; Wen Yang; Chunmei Geng; Kangwei Li (Atmospheric Environment, 2023)

Remodeled CD146+CD271+ Bone Marrow Mesenchymal Stem Cells from Patients with Polycythemia Vera Exhibit Altered Hematopoietic Supportive Activity - Chao Chen; Mingying Zhang; Rong Li; Jiajia Yuan; Jinqiang Yan; Yuhui Zhang; Wen Xing; Jie Bai; Yuan Zhou (Stem Cell Reviews and Reports, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Large-scale testing of the mortise and tenon joint performance of the tunnel lining of prefabricated frame tunnels - Zhen Huang; Hai-wen Bai; Shao-kun Ma; Jia-wei Zhang; Yi-miao Chen; Hong-zhou Li (Tunnelling and Underground Space Technology, 2023)

Broad-specificity antibody profiled by hapten prediction and its application in immunoassay for fipronil and major metabolites - Peipei Li; Yuchen Bai; Haiyang Jiang; Yingjie Zhang; Yuan Li; Changfei Duan; Kai Wen; Xuezhi Yu; Zhanhui Wang (Journal of Hazardous Materials, 2023)

Effects of different pretreatment methods on drying kinetics, three-dimensional deformation, quality characteristics and microstructure of dried apple slices - Jun-Wen Bai; Lu Zhang; Joshua H. Aheto; Jian-Rong Cai; Yu-Chi Wang; Li Sun; Xiao-Yu Tian (Innovative Food Science & Emerging Technologies, 2023)

Co-pyrolysis behaviors of coal and polyethylene by combining in-situ Py-TOF-MS and reactive molecular dynamics - Wei Feng; Mo Zheng; Lijun Jin; Jin Bai; Lingxue Kong; Huaizhu Li; Zongqing Bai; Wen Li (Fuel, 2023)

UHPLC-QTOF-MS-based untargeted metabolomics and mineral element analysis insight into the geographical differences of Chrysanthemum morifolium Ramat cv. “Hangbaiju” from different origins - Wanjun Long; Xiuyun Bai; Siyu Wang; Hengye Chen; Xiao-Li Yin; Hui-Wen Gu; Jian Yang; Haiyan Fu (Food Research International, 2023)

Novel insights into the catalytic effect of hydrogen bonds on aldehyde groups generation during direct coal liquefaction - Ranran Hou; Zongqing Bai; Xing Fan; Peng Liang; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Fuel, 2023)

In-situ catalytic upgrading of Hami coal pyrolysis volatiles over acid-modified kaolin - Yujie Hou; Zongqing Bai; Hao Lu; Zhihao Feng; Tingting Zhang; Yuxing Jia; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Fuel, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

A high-efficient and low-consumption nanoimprint method to prepare large-area and high-quality Nafion array for the ordered MEA of fuel cell - Yali Li; Qinglin Wen; Jiaqi Qin; Siyi Zou; Fandi Ning; Chuang Bai; Saifei Pan; Hanqing Jin; Pengpeng Xu; Min Shen; YuJiang Song; Xiaochun Zhou. (Chemical Engineering Journal, 2023)

MdbHLH51 plays a positive role in anthocyanin accumulation in ‘Red Delicious’ apples - Gai-Xing Ning; Wen-Fang Li; Ming-Yu Chu; Zong-Huan Ma; Ping Wang; Juan Mao; Bai-Hong Chen (Trees, 2022)

Structural deformation, metallogenic epoch and genetic mechanism of the Woxi Au-Sb-W deposit, Western Hunan Province, South China - Bin Li; Deru Xu; Daoyuan Bai; Guoxiang Chi; Junfeng Dai; Cheng Gao; Teng Deng; Shaohao Zou; Wen Ma; Guojian Wang; Yuexin Ling; Guangqian Zeng; et al. (Science China Earth Sciences, 2022)

Exposure to Source-Specific Particulate Matter and Health Effects: a Review of Epidemiological Studies - Jia Xu; Peng Wang; Tiantian Li; Guoliang Shi; Meng Wang; Lei Huang; Shaofei Kong; Jicheng Gong; Wen Yang; Xinhua Wang; Chunmei Geng; Bin Han; et al. (Current Pollution Reports, 2022)

Toward improvements for enhancement the productivity and color value of Monascus pigments: a critical review with recent updates - JinTao He; MingXi Jia; Wen Li; Jing Deng; JiaLi Ren; FeiJun Luo; Jie Bai; Jun Liu (Critical Reviews in Food Science and Nutrition, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Early landslide mapping with slope units division and multi-scale object-based image analysis — A case study in the Xianshui River basin of Sichuan, China - Hui Gao; Li He; Zheng-wei He; Wen-qian Bai (Journal of Mountain Science, 2022)

An integrated belowground trait‐based understanding of nitrogen‐driven plant diversity loss - Qiuying Tian; Peng Lu; Xiufeng Zhai; Ruifang Zhang; Yao Zheng; Hong Wang; Bao Nie; Wenming Bai; Shuli Niu; Peili Shi; Yuanhe Yang; Kaihui Li; et al. (Global Change Biology, 2022)
Belowground plant traits play important roles in plant diversity loss driven by atmospheric nitrogen (N) deposition. However, the way N enrichment shapes plant microhabitats by patterning belowground traits and finally determines aboveground responses is poorly understood. Here, we investigated the rhizosheath trait of 74 plant species in seven N‐addition simulation experiments across multiple grassland ecosystems in China. We found that rhizosheath formation differed among plant functional groups and contributed to changes in plant community composition induced by N enrichment. Compared with forb species, grass and sedge species exhibited distinct rhizosheaths; moreover, grasses and sedges expanded their rhizosheaths with increasing N‐addition rate which allowed them to colonize belowground habitats. Grasses also shaped a different microenvironment around their roots compared with forbs by affecting the physicochemical, biological, and stress‐avoiding properties of their rhizosphere soil. Rhizosheaths act as a “biofilm‐like shield” by the accumulation of protective compounds, carboxylic anions and polysaccharides, determined by both plants and microorganisms. This enhanced the tolerance of grasses and sedges to stresses induced by N enrichment. Conversely, forbs lacked the protective rhizosheaths which renders their roots sensitive to stresses induced by N enrichment, thus contributing to their disappearance under N‐enriched conditions. This study uncovers the processes by which belowground facilitation and trait matching affect aboveground responses under conditions of N enrichment, which advances our mechanistic understanding of the contribution of competitive exclusion and environmental tolerance to plant diversity loss caused by N deposition.

Litter nitrogen concentration changes mediate effects of drought and plant species richness on litter decomposition - Jiang Wang; Yuan Ge; Johannes H. C. Cornelissen; Xiao-Yan Wang; Song Gao; Yi Bai; Tong Chen; Zhong-Wang Jing; Chong-Bang Zhang; Wen-Li Liu; Jun-Min Li; Fei-Hai Yu (Oecologia, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Responses of soil pH to no‐till and the factors affecting it: A global meta‐analysis - Xin Zhao; Cong He; Wen‐Sheng Liu; Wen‐Xuan Liu; Qiu‐Yue Liu; Wei Bai; Li‐Jun Li; Rattan Lal; Hai‐Lin Zhang (Global Change Biology, 2022)
No‐till (NT) is a sustainable option because of its benefits in controlling erosion, saving labor, and mitigating climate change. However, a comprehensive assessment of soil pH response to NT is still lacking. Thus, a global meta‐analysis was conducted to determine the effects of NT on soil pH and to identify the influential factors and possible consequences based on the analysis of 114 publications. When comparing tillage practices, the results indicated an overall significant decrease by 1.33 ± 0.28% in soil pH under NT than that under conventional tillage ( p −1 (−1.83%), or crop residue retention (−1.52%). Changes in organic matter decomposition under undisturbed soil and with crop residue retention might lead to a higher concentration of H + and lower of basic cations (i.e., calcium, magnesium, and potassium), which decrease the soil pH, and consequently, impact nutrient dynamics (i.e., soil phosphorus) in the surface layer under NT. Furthermore, soil acidification may be aggravated by NT within site‐specific conditions and improper fertilizer and crop residue management and consequently leading to adverse effects on soil nutrient availability. Thus, there is a need to identify strategies to ameliorate soil acidification under NT to minimize the adverse consequences.

Expression and Characterization of a Potent Long-Acting GLP-1 Receptor Like Agonist, Exendin-4-Fc - Wen Zhang; Ming Li; Yanlu Zan; Yi Bai (International Journal of Peptide Research and Therapeutics, 2021)
Human GLP-1 (glucagon-like peptide-1) can produce a remarkable improvement in glycemic control in patients with type 2 diabetes. However, its clinical benefits are limited by its short half-life, which is less than 2 min because of its small size and rapid enzymatic inactivation by dipeptidyl peptidase IV. We engineered Exendin-4-Fc, a 66-kDa fusion protein by linking an IgG2 Fc to Exendin-4. A stably transfected Chinese hamster ovary cell line was obtained using electroporation. Exendin-4-Fc stimulated insulin secretion in INS-1 cells in a dose- and glucose-dependent manner and increased insulin mRNA expression. The plasma half-life of Exendin-4-Fc in cynomolgus monkeys was approximately 133.92 ± 25.1 h. In the KKAy mouse model of diabetes, one intraperitoneal injection of Exendin-4-Fc (1 mg/kg) reduced blood glucose levels for 5 days. A 4-week repeat-administration study identified sustained effects on blood glucose levels. Oral glucose tolerance tests conducted at the beginning and end of this 4-week period showed that Exendin-4-Fc produced a stable glucose lowering effect. In addition, KKAy mice treated with Exendin-4-Fc showed statistically significant weight loss from day 23. In conclusion, these properties of Exendin-4-Fc demonstrated that it could be a potential long-acting GLP-1 receptor agonist for the treatment of type 2 diabetes.

Influences of environmental factors on the modern 14C reservoir effects in Qinghai-Tibet Plateau lakes - Ding-ding Du; Zhi-wen Li; Hai-ping Hu; Yong-hui Bai; Wen Li; Muhammad Saleem Mughal; Hai-Yan Qian (Journal of Mountain Science, 2021)

Evaluation of watershed soil erosion hazard using combination weight and GIS: a case study from eroded soil in Southern China - Shifa Chen; Wen Liu; Yonghui Bai; Xiaoying Luo; Hangfei Li; Xuan Zha (Natural Hazards, 2021)

A new ergostane derivative from the leaves of Heynea trijuga Roxburgh - Shou-Bai Liu; Zheng Cui; Hui-Qin Chen; Hao Wang; Wen-Hua Dong; Cai-Hong Cai; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2021)

Autophagy induced by H. pylori VacA regulated the survival mechanism of the SGC7901 human gastric cancer cell line - Juan Luo; Luyan Bai; Jun Tao; Yu Wen; Mingke Li; Yunzhen Zhu; Sufeng Luo; Guangyu Pu; Lanqing Ma (Genes & Genomics, 2021)
Background Vacuolating cytotoxin (VacA) is an important virulence factor of Helicobacter pylori ( H. pylori ). It was previously believed that VacA can trigger the cascade of apoptosis on mitochondria to lead to cell apoptosis. Recently, it was found that VacA can induce autophagy. However, the molecular mechanism by which VacA induces autophagy is largely unknown. Objective We aimed to explore the molecular mechanism of autophagy induced by H. pylori in gastric cancer cells and the effect of autophagy on the survival of gastric cancer cells. Methods The autophagy of human gastric cancer cell line SGC7901 was detected by Western blot and RT-PCR in the treatment of VacA protein of H. pylori . The relationship between autophagy and reactive oxygen species (ROS) in the proliferation of gastric cancer cells were studied by gene expression silences (siRNA) and CM-H2DCFDA (DCF) staining. Results The results showed that VacA protein secreted by H. pylori in the supernatant stimulated autophagy in SGC7901 cells. After VacA protein treatment, the mRNA expressions of BECN1, ATG7 and PIK3C3, were up-regulated. ATG7 silencing by siRNA inhibited VacA-induced autophagy. Furthermore, our data demonstrated that VacA protein increased ROS levels. Addition of the antioxidant N -acetyl- l -cysteine (NAC) suppressed the levels of ROS, leading to inhibition of autophagy. Conclusions H. pylori VacA is a key toxin that induces autophagy by increased ROS levels. And our findings demonstrated that VacA significantly inhibited proliferation in SGC7901 cells.

Relationship between crustal magnetic anomalies and strong earthquake activity in the south segment of the China North-South Seismic Belt - Li-Min Wen; Guo-Fa Kang; Chun-Hua Bai; Guo-Ming Gao (Applied Geophysics, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Design, synthesis and evaluation of dihydrotriazine derivatives-bearing 5-aryloxypyrazole moieties as antibacterial agents - Tian-Yi Zhang; Chun-Shi Li; Ming-Yue Cui; Xue-Qian Bai; Jiang-Hui Chen; Ze-Wen Song; Bo Feng; Xue-Kun Liu (Molecular Diversity, 2021)

Rosanortriterpenes A–B, two new nortriterpenes from the fruits of Rosa laevigata var. leiocapus - Yu-Nong Tian; Bai-Lin Li; Juan-Juan Hu; Jin-Dan Xie; Wen-Jing Xiao; Ling-Hui Nie; Jie-Wei Wu (Natural Product Research, 2021)

Exogenous ABA and its inhibitor regulate flower bud induction of apple cv. ‘Nagafu No. 2′ grafted on different rootstocks - Wen-Fang Li; Juan Mao; Jing Su; Xin-Wen Li; Mohammed Mujitaba Dawuda; Zong-Huan Ma; Cun-Wu Zuo; Ze-Shan An; Bai-Hong Chen (Trees, 2021)

Simvastatin Enhances Muscle Regeneration Through Autophagic Defect-Mediated Inflammation and mTOR Activation in G93ASOD1 Mice - Yafei Wang; Lin Bai; Shuai Li; Ya Wen; Qi Liu; Rui Li; Yaling Liu (Molecular Neurobiology, 2021)

Impact of farmers’ livelihood behavior on soil erosion in hilly areas—a comparison between erosion controlled and uncontrolled areas of southern China - Shifa Chen; Yonghui Bai; Hangfei Li; Wen Liu (Arabian Journal of Geosciences, 2021)

Studies of anticancer activity in vivo and in vitro behaviors of liposomes encapsulated iridium(III) complex - Yiying Gu; Haoyu Wen; Yuanyuan Zhang; Lan Bai; Yi Zhou; Huiwen Zhang; Li Tian; Jing Hao; Yunjun Liu (JBIC Journal of Biological Inorganic Chemistry, 2021)

Allotransplantation of adult spinal cord tissues after complete transected spinal cord injury: Long-term survival and functional recovery in canines - He Shen; Shuyu Wu; Xi Chen; Bai Xu; Dezun Ma; Yannan Zhao; Yan Zhuang; Bing Chen; Xianglin Hou; Jiayin Li; Yudong Cao; Xianyong Fu; et al. (Science China Life Sciences, 2020)

Synthesis and molecular docking studies of novel pyrimidine derivatives as potential antibacterial agents - Xue-Qian Bai; Chun-Shi Li; Ming-Yue Cui; Ze-Wen Song; Xing-Yu Zhou; Chao Zhang; Yang Zhao; Tian-Yi Zhang; Tie-Yan Jiang (Molecular Diversity, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Gelsemine, a natural alkaloid extracted from Gelsemium elegans Benth. alleviates neuroinflammation and cognitive impairments in Aβ oligomer-treated mice - Liping Chen; Hanbo Pan; Yujing Bai; Huiqin Li; Wen Yang; Zhi-Xiu Lin; Wei Cui; Yan-Fang Xian (Psychopharmacology, 2020)

Sources and ore-forming fluid pathways of carbonate-hosted Pb–Zn deposits in Southwest China: implications of Pb–Zn–S–Cd isotopic compositions - Chong Xu; Hong Zhong; Rui-Zhong Hu; Han-Jie Wen; Wei-Guang Zhu; Zhong-Jie Bai; Hai-Feng Fan; Fang-Fang Li; Ting Zhou (Mineralium Deposita, 2020)

Lysobacter oculi sp. nov., isolated from human Meibomian gland secretions - Hua Bai; Huibin Lv; Aihua Deng; Xiaodan Jiang; Xuemin Li; Tingyi Wen (Antonie van Leeuwenhoek, 2020)

Whole-genome DNA methylation patterns and complex associations with gene expression associated with anthocyanin biosynthesis in apple fruit skin - Wen-Fang Li; Gai-Xing Ning; Juan Mao; Zhi-Gang Guo; Qi Zhou; Bai-Hong Chen (Planta, 2019)

Effects of CEPA and 1-MCP on Flower Bud Differentiation of Apple cv. ‘Nagafu No.2’ Grafted on Different Rootstocks - Wen-Fang Li; Juan Mao; Xin-Wen Li; Jing Su; Mohammed Mujitaba Dawuda; Zong-Huan Ma; Cun-Wu Zuo; Ze-Shan An; Bai-Hong Chen (Journal of Plant Growth Regulation, 2019)

CTHRC1 promotes M2-like macrophage recruitment and myometrial invasion in endometrial carcinoma by integrin-Akt signaling pathway - Lu-Ying Li; Ke-Min Yin; Yi-Han Bai; Zhi-Gang Zhang; Wen Di; Shu Zhang (Clinical & Experimental Metastasis, 2019)

A new insecticidal havanensin-type limonoid from the roots of Trichilia sinensis Bentv. - Shou-Bai Liu; Hui-Qin Chen; Gang Feng; Zhi-Kai Guo; Cai-hong Cai; Jun Wang; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2018)

Aircraft Measurement of Chemical Characteristics of PM2.5 over the Yangtze River Area in China - Lihong Ren; Renjian Zhang; Xiaoyang Yang; Chunmei Geng; Wei Wang; Shiro Hatakeyama; Hong Li; Wen Yang; Zhipeng Bai; Akinori Takami; Hongjie Liu; Jianhua Chen (Aerosol Science and Engineering, 2018)

Serum Oxidative Stress Marker Levels in Unmedicated and Medicated Patients with Schizophrenia - Zhi-Le Bai; Xue-Song Li; Guang-Yang Chen; Yang Du; Ze-Xu Wei; Xi Chen; Guang-En Zheng; Wen Deng; Yong Cheng (Journal of Molecular Neuroscience, 2018)

Polymorphisms of peroxisome proliferator-activated receptor γ (PPARγ) and cluster of differentiation 36 (CD36) associated with valproate-induced obesity in epileptic patients - Xupeng Bai; Chuncao Xu; Dingsheng Wen; Yibei Chen; Hongliang Li; Xueding Wang; Liemin Zhou; Min Huang; Jing Jin (Psychopharmacology, 2018)

Expression of ASIC3 in the Trigeminal Nucleus Caudalis Plays a Role in a Rat Model of Recurrent Migraine - Sha Wang; Bai-Xue Wu; Chao-Yang Liu; Guang-Cheng Qin; Wen-Hui Yan; Ji-Ying Zhou; Li-Xue Chen (Journal of Molecular Neuroscience, 2018)

Novel method for iron recovery from hazardous iron ore tailing with induced carbothermic reduction-magnetic flocculation separation - Shao-Jun Bai; Chun-Long Li; Xiang-Yu Fu; Chao Lv; Shu-Ming Wen (Clean Technologies and Environmental Policy, 2018)

Responses of soil microbial community to nitrogen fertilizer and precipitation regimes in a semi-arid steppe - Yi-Fei Sun; Ju-Pei Shen; Cui-Jing Zhang; Li-Mei Zhang; Wen-Ming Bai; Ying Fang; Ji-Zheng He (Journal of Soils and Sediments, 2018)

The persistent prevalence and evolution of cross-family recombinant coronavirus GCCDC1 among a bat population: a two-year follow-up - Joseph O. Obameso; Hong Li; Hao Jia; Min Han; Shiyan Zhu; Canping Huang; Yuhui Zhao; Min Zhao; Yu Bai; Fei Yuan; Honglan Zhao; Xia Peng; et al. (Science China Life Sciences, 2017)

Distribution of heavy metals in maize and mudflat saline soil amended by sewage sludge - Yan-Chao Bai; Wen-Gang Zuo; Hai-Tao Zhao; Li-Juan Mei; Chuan-Hui Gu; Yong-Xiang Guan; Xu-Kui Wang; Min-Jing Gu; Cai-Yun Zang; Yu-Hua Shan; Ke Feng (Journal of Soils and Sediments, 2017)

Elemental and Sr–Nd isotopic geochemistry of Permian Emeishan flood basalts in Zhaotong, Yunnan Province, SW China - Juan Li; Hong Zhong; Wei-Guang Zhu; Zhong-Jie Bai; Wen-Jun Hu (International Journal of Earth Sciences, 2017)

A comparative study of strontium-substituted hydroxyapatite coating on implant’s osseointegration for osteopenic rats - Zhou-Shan Tao; Bing-Li Bai; Xing-Wen He; Wei Liu; Hang Li; Qiang Zhou; Tao Sun; Zheng-Liang Huang; Kai-kai Tu; Yang-Xun Lv; Wei Cui; Lei Yang (Medical & Biological Engineering & Computing, 2016)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Effects of seasonal variations on soil microbial community composition of two typical zonal vegetation types in the Wuyi Mountains - Ze-yan Wu; Wen-xiong Lin; Jian-juan Li; Jin-fu Liu; Bai-lian Li; Lin-kun Wu; Chang-xun Fang; Zhi-xing Zhang (Journal of Mountain Science, 2016)

Zebrafish Embryo Toxicity Microscale Model for Ichthyotoxicity Evaluation of Marine Natural Products - Hong Bai; Wen-Wen Kong; Chang-Lun Shao; Yun Li; Yun-Zhang Liu; Min Liu; Fei-Fei Guan; Chang-Yun Wang (Marine Biotechnology, 2016)

Large-scale comparative phosphoprotein analysis of maize seedling leaves during greening - De-Li Ning; Ke-Hui Liu; Chang-Cai Liu; Jin-Wen Liu; Chun-Rong Qian; Yang Yu; Yue-Feng Wang; Ying-Chun Wang; Bai-Chen Wang (Planta, 2016)

A novel soil manganese mechanism drives plant species loss with increased nitrogen deposition in a temperate steppe - Qiuying Tian; Nana Liu; Wenming Bai; Linghao Li; Jiquan Chen; Peter B. Reich; Qiang Yu; Dali Guo; Melinda D. Smith; Alan K. Knapp; Weixin Cheng; Peng Lu; et al. (Ecology, 2016)
Loss of plant diversity with increased anthropogenic nitrogen (N) deposition in grasslands has occurred globally. In most cases, competitive exclusion driven by preemption of light or space is invoked as a key mechanism. Here, we provide evidence from a 9‐yr N‐addition experiment for an alternative mechanism: differential sensitivity of forbs and grasses to increased soil manganese (Mn) levels. In Inner Mongolia steppes, increasing the N supply shifted plant community composition from grass–forb codominance (primarily Stipa krylovii and Artemisia frigida , respectively) to exclusive dominance by grass, with associated declines in overall species richness. Reduced abundance of forbs was linked to soil acidification that increased mobilization of soil Mn, with a 10‐fold greater accumulation of Mn in forbs than in grasses. The enhanced accumulation of Mn in forbs was correlated with reduced photosynthetic rates and growth, and is consistent with the loss of forb species. Differential accumulation of Mn between forbs and grasses can be linked to fundamental differences between dicots and monocots in the biochemical pathways regulating metal transport. These findings provide a mechanistic explanation for N‐induced species loss in temperate grasslands by linking metal mobilization in soil to differential metal acquisition and impacts on key functional groups in these ecosystems.

Emodin affects biofilm formation and expression of virulence factors in Streptococcus suis ATCC700794 - Yan-Bei Yang; Shuai Wang; Chang Wang; Quan-Yong Huang; Jing-Wen Bai; Jian-Qing Chen; Xue-Ying Chen; Yan-Hua Li (Archives of Microbiology, 2015)

Establishment and characterization of fin cell lines from diploid, triploid, and tetraploid oriental weatherfish (Misgurnus anguillicaudatus) - Xia Li; Chen Ma; Yan-Jie Qin; Ya-Juan Li; Di Wu; Li-Wen Bai; Ai-Jun Pei (Fish Physiology and Biochemistry, 2015)

Research and experimental testing of a new kind electrokinetic logging tool - Feng-Bo Li; Xiao-Dong Ju; Wen-Xiao Qiao; Jun-Qiang Lu; Bai-Rong Men (Applied Geophysics, 2014)

Continuous evolution of avian infectious bronchitis virus resulting in different variants co-circulating in southern China - Meng Li; Mei-Lan Mo; Bai-Cheng Huang; Wen-Sheng Fan; Zheng-Ji Wei; Tian-Chao Wei; Kang-Ran Li; Ping Wei (Archives of Virology, 2013)

Label-free quantitative proteomics analysis of dormant terminal buds of poplar - De-Li Ning; Chang-Cai Liu; Jin-Wen Liu; Zhuo Shen; Su Chen; Feng Liu; Bai-Chen Wang; Chuan-Ping Yang (Molecular Biology Reports, 2013)

Synthesis, molecular modeling, and biological evaluation of 1,2,4-triazole derivatives containing pyridine as potential anti-tumor agents - Yan-Bin Zhang; Wen Liu; Yu-Shun Yang; Xiao-Liang Wang; Hai-Liang Zhu; Li-Fei Bai; Xiao-Yang Qiu (Medicinal Chemistry Research, 2013)

Encoding of rat working memory by power of multi-channel local field potentials via sparse non-negative matrix factorization - Xu Liu; Tiao-Tiao Liu; Wen-Wen Bai; Hu Yi; Shuang-Yan Li; Xin Tian (Neuroscience Bulletin, 2013)

Genetic diversity and sampling strategy of Scutellaria baicalensis germplasm resources based on ISSR - Chengke Bai; Miaomiao Wen; Longjin Zhang; Guishuang Li (Genetic Resources and Crop Evolution, 2013)

A mutation in a coproporphyrinogen III oxidase gene confers growth inhibition, enhanced powdery mildew resistance and powdery mildew-induced cell death in Arabidopsis - Chuan-yu Guo; Guang-heng Wu; Jin Xing; Wen-qi Li; Ding-zhong Tang; Bai-ming Cui (Plant Cell Reports, 2013)

Geology and ages of porphyry and medium- to high-sulphidation epithermal gold deposits of the continental margin of Northeast China - Shi-Jiong Han; Jing-Gui Sun; Ling-An Bai; Shu-Wen Xing; Peng Chai; Yong Zhang; Fan Yang; Lan-Jing Men; Yi-Xin Li (International Geology Review, 2013)

Dysregulation of the β3 integrin-VEGFR2 complex in Hantaan virus–directed hyperpermeability upon treatment with VEGF - Wei Wang; Ye Zhang; Yu Li; Lei Pan; Lu Bai; Yan Zhuang; Chang-Xing Huang; Jiu-Ping Wang; Hai-Tao Yu; Xin Wei; Wei Jiang; Ya-Yun Nan; et al. (Archives of Virology, 2012)

Determination S-Genotypes and Identification of Five Novel S-RNase Alleles in Wild Malus Species - Tianzhong Li; Shenshan Long; Maofu Li; Songling Bai; Wen Zhang (Plant Molecular Biology Reporter, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Overexpression of the trehalose-6-phosphate synthase gene OsTPS1 enhances abiotic stress tolerance in rice - Hao-Wen Li; Bai-Sheng Zang; Xing-Wang Deng; Xi-Ping Wang (Planta, 2011)

Quantitative trait loci for rice yield-related traits using recombinant inbred lines derived from two diverse cultivars - XU FENG BAI; LI JUN LUO; WEN HAO YAN; MALLIKARJUNA RAO KOVI; YONG ZHONG XING (Journal of Genetics, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Phenotypic and Genotypic Characterization Vibrio cholerae O139 of Clinical and Aquatic Isolates in China - Bai-sheng Li; Hai-ling Tan; Duo-chun Wang; Xiao-ling Deng; Jing-diao Chen; Hao-jie Zhong; Bi-xia Ke; Chang-wen Ke; Biao Kan (Current Microbiology, 2011)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Lead and Other Elemental Content of Normal and Erwinia carotovora Infected Amorphallus konjac Corms - Tao Li; Wen-Guo Wei; Wei Shao; Bai-Ling Chen; Ying-Ping Huang (Bulletin of Environmental Contamination and Toxicology, 2010)

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

ZNF418, a novel human KRAB/C2H2 zinc finger protein, suppresses MAPK signaling pathway - Yongqing Li; Dan Yang; Yan Bai; Xiaoyang Mo; Wen Huang; Wuzhou Yuan; Zhaochu Yin; Yun Deng; Oleg Murashko; Yuequn Wang; Xiongwei Fan; Chuanbing Zhu; et al. (Molecular and Cellular Biochemistry, 2008)

Spatial variability of Soil Nutrients and Influencing Factors in a Vegetable Production Area of Hebei Province in China - Shao-Wen Huang; Ji-Yun Jin; Li-Ping Yang; You-Lu Bai (Nutrient Cycling in Agroecosystems, 2006)

Nitrogen response efficiency increased monotonically with decreasing soil resource availability: a case study from a semiarid grassland in northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Shi-Ping Chen; Zheng-Wen Wang; Quan-Sheng Chen; Wen-Ming Bai (Oecologia, 2006)

Characterization of HoMADS 1 and its induction by plant hormones during in vitro ovule development in Hyacinthus orientalis L. - Hong Xu; Xing Li; Quan Li; Shu Bai; Wen Lu; Xian Zhang (Plant Molecular Biology, 2004)

Isolation of HAG1 and its regulation by plant hormones during in vitro floral organogenesis in Hyacinthus orientalis L. - Quan Li; Xing Li; Shu Bai; Wen Lu; Xian Zhang (Planta, 2002)